Multi-omics analysis reveals concentration-specific mechanisms underlying nanoplastic-induced muscle dysfunction and locomotor impairment in large yellow croaker - Siping Li; Yuhe Yang; Keji Jiang; Cuihua Wang; Yazhou Jiang; Xin Liu; Yuanhao Ren; Tingting Lin; Quanyou Guo (Aquaculture, 2027)

Simulation of equivalent scale-up design of molten salt electrolyzer with stirrer using dimensional analysis and numerical method - Meng Zhang; Lunxiu Cao; Yuannuo Wang; Hemu Zhao; Yi Li; Wenlong Huang; Hongguo Hou; Chunyuan Zhan; Tingting Liu; Jingyang Wang; Rushan Lin; Yu Zhou; et al. (Annals of Nuclear Energy, 2026)

Assessment of reproductive risks of bisphenol S in male BALB/c mice through functional histological and multi-omics investigations - Xiaotan Lin; Huan Liu; Wei Ma; Shuo Lu; Bo Li; Wen Zhang; Ning Li; Tingting Chen (Food and Chemical Toxicology, 2026)

Broodstock pairing density as a management strategy to modulate behavior and enhance reproductive efficiency in the pot-bellied seahorse (Hippocampus abdominalis) - Fengyuan Shen; Guangjie Fang; Hui Xu; Yuanhao Ren; Siping Li; Lingzhi Li; TingTing Lin (Applied Animal Behaviour Science, 2026)

Aerobic biodegradation of cefpirome sulfate by Sphingomonas melonis P33: Performance, pathways, and genomic characterization - Yuyang Wang; Hongchao Min; Qi Wang; Tingting Zhang; Yin Li; Jiayu Zhang; Lin Lin; Xiaoyan Li; Bing Li (Journal of Water Process Engineering, 2026)

From temperature to VPD: shifting drivers of flash droughts amplify ecosystem risks in high-latitude cold climates - Long Qi; Chunyu Dong; Tingting Chen; Kairong Lin; Lei Chen; Xiaohong Chen (Journal of Hydrology, 2026)

Dual isoflavone and carboxyl-containing compound profiling for antioxidant evaluation of fermented soybean products - Yuetong Jiang; Yuye Gao; Xiaojing Liu; Congcong Gao; Wen Yang; Tian Tian; Yujia Zhai; Fangyuan Gao; Yunxia Li; Wenjing Zhang; Zhi Chai; Jian-lin Wu; et al. (Food Research International, 2026)

Molecular dynamics-guided titanium platform with chitosan-assisted bacterial anchoring for sequential antibacterial and osteogenic functions - Jiaying Li; Junkai Hu; Jiamin Li; Weihan Zheng; Jiejie Wang; Tao Lin; Jiahao Pu; Tingting Chen; Mingrui Li; Hang Sang; Jianlin Shen; Lincong Luo; et al. (Chemical Engineering Journal, 2026)

Postbiotics mitigate translucent post-larvae disease (TPD) in Penaeus vannamei by reinforcing hepatopancreatic cytoskeletal integrity against VHVP-2 toxin - Wenqiang Li; Shuang Liu; Jin Yan; Ping Li; Tingting Xu; Jin-Seng Lin; Hsiao-Tung Chang; Ting-Yu Lee; Qingli Zhang (Aquaculture, 2026)

Soil organic carbon, soil heterotrophic respiration, and microbial community assembly in response to vegetation restoration in the karst area of Southwest China - Tongqing Su; Geng Lin; Dan Chen; Tingting Cui; Jianbing Zhang; Weiqun Luo; Baoqing Hu (Pedobiologia, 2026)

Resolving stratified Pb and Cr hazards in 3D at an abandoned steel complex: A heterogeneity-learning approach to risk-based remediation - Maogui Hu; Guoxing Ye; Lin Jia; Guanlin Guo; Tingting Fang; Ruicong Zhang; Jinfeng Wang (Journal of Hazardous Materials, 2026)

Pathogen survival and antibiotic resistance gene persistence on hospital environmental surfaces: Short-lived disinfection efficacy may enables persistent contamination threat - Yunhan Jiang; Haiting Feng; Xiaoguang Guo; Bingni Zhang; Zhihao Lin; Jiyan Shi; Tingting Qu; Yunbo Chen; Chaofeng Shen (Building and Environment, 2026)

R2R3-MYB transcription factor MYB113 specifically regulates anthocyanin accumulation in Lycium ruthenicum - Tingting Li; Zihan Zhang; Jingjin Wang; Huan Qin; Lin Tang (Plant Cell Reports, 2026)

Peak-at-Intermediate-Salinity Transcriptional and Histological Responses of Triploid Rainbow Trout Gills to Salinity Gradients - Yanming Sui; Jingtao Liu; Haopeng Hu; Yan Ji; Yuanhao Ren; Bo Qin; Na Ying; Tingting Lin; Siping Li; Hanfeng Zheng; Lei Li (Fishes, 2026)
Using a three-factor orthogonal design, we investigated the transcriptomic and histological responses of triploid rainbow trout (Oncorhynchus mykiss) gills across three salinities (10, 20, and 30 ppt) over 60 days, with temperature and body size as background conditions. Results showed that 20 ppt was associated with extensive transcriptional reprogramming, with 3333 differentially expressed transcripts (DETs), whereas 30 ppt induced only 120 DETs; WGCNA further identified salinity-correlated modules involved in ion transport and ribosome biogenesis. Histological alterations remained within physiological ranges with no salinity-dependent severity gradient, as confirmed by semi-quantitative scoring. These findings demonstrate that triploid rainbow trout gills employ distinct molecular strategies at medium versus high salinity. Within the 10–30 ppt range examined, 20 ppt was the salinity at which transcriptional reprogramming was most active, suggesting that this intermediate salinity warrants further investigation as a potential acclimation stage.

Oncorhynchus mykiss as a Salmonid Functional Genomics Model: A Structured Narrative Review of Genomic Resources, Mucosal Immunity, Disease Resistance, Environmental Stress, and Causal Validation - Zhongquan Jiang; Sijia Wu; Yong Zheng; Di Peng; Siping Li; Yuanhao Ren; Bo Qin; Hanfeng Zheng; Lei Li; Tingting Lin (Fishes, 2026)
Rainbow trout (Oncorhynchus mykiss) is an important cold-water aquaculture species and a tractable salmonid model for functional genomics. Rapid advances in chromosome-level genome assemblies, genetic variation resources, regulatory annotations, tissue and cell models, controlled challenge systems, and genome-editing technologies have established an increasingly integrated framework for linking genomic variation with measurable phenotypes. Evidence from studies of mucosal immunity, disease-resistance genetics, and environmental stress responses indicates that these resources can improve candidate-gene prioritization and mechanistic interpretation across molecular, cellular, tissue, and whole-fish levels. However, differential gene expression, quantitative trait locus and genome-wide association signals, genomic predictions, and cell-type localization remain largely associative and rarely provide direct evidence of causality. Interpretation is further complicated by salmonid-specific whole-genome duplication, because retained paralogues may exhibit tissue-specific divergence, functional redundancy, and compensatory responses. Further progress will require the integration of pangenomics, regulatory annotation, single-cell and spatial analyses, and paralogue-aware functional perturbation in both cell-based and whole-fish systems. Such integration will strengthen causal inference, clarify genotype–phenotype relationships, and support disease-resistant breeding, healthy aquaculture, and environmental risk assessment.

ADAMTS7 selective inhibitor BAY-9835 alleviates acute myocardial infarction by suppressing the NF-κB-mediated pyroptosis - Yunzhi Ling; Yang Lyu; Hanchuan Chen; Biting Lin; Gengyu Zhou; Simiao Chen; Tingting Weng; Ziqing Ruan; Yuanfan Zhu; Zhaoju Zhu; Yansong Guo; Kaiyang Lin (Toxicology and Applied Pharmacology, 2026)

Fecal pollution source tracking at a marine bathing beach: A case study of Beihai Silver Beach - Hongxia Ming; Ziqi Chen; Tingting Shi; Zhongzhi Chen; Wenjing Pan; Jiannan Lin; Jie Su; Jingfeng Fan (Regional Studies in Marine Science, 2026)

Rare earth nanoparticles: Illuminating the future of precision photodynamic therapy in oncology - Han Wang; Zhiwei Li; Jun Liao; Qi Nie; Qianli Lin; Tingting Qi; Xiao Luo (Journal of Photochemistry and Photobiology B: Biology, 2026)

Wettability-switchable deep bed filtration for efficient oily wastewater treatment - Song Xichen; Yan Yaping; Zhang Tingting; Zhou Jianqiang; Wang Xiaojuan; Wang Zhezhe; Lin Jialong; Wang Ting; Song Xiaosan; Dai Liang; Wang Gang; Gao Suxia; et al. (Journal of Hazardous Materials, 2026)

Enzyme-immobilized metal-organic framework biosensor for target-triggered sensitive fluorescence detection of diazinon residue and accumulation in rice - Tingting Cai; Yiran Li; Jiale Song; Lin Zhou; Zitong Wang; Binshuo Guo; Jie Gao; Guanghao Chen; Jintong Liu; Hong Yang (Journal of Cleaner Production, 2026)

Genomic insights into high GABA production by Levilactobacillus brevis Q3–11 and its application in developing functional kiwifruit juice - Bingrui Guo; Qi Wu; Xu Yan; Wei Ji; Shufeng Yin; Sufang Zhang; Yiwei Dai; Xiangyu Sun; Tingting Ma; Xinping Lin (International Journal of Food Microbiology, 2026)

Perovskite-based flexible films for high-energy radiation shielding and detection - Jinlong Bai; Weiqiang Gong; Yi Zhao; Zizheng Li; Yi Chang; Ziming Wang; Tingting Liu; Xinci Zhang; Xitian Zhang; Feng Gao; Lin Li (Chemical Engineering Journal, 2026)

3D-printed Li-HA composite scaffold with staged simvastatin/NGF delivery and continuous Li+ signaling enhances immune–neuro–angiogenic coupling for bone repair - Xianglei Mo; Tengbin Shi; Siyi Huang; Dongyi Mai; Lingyu Kong; Junkai Mi; Zongqiang Gao; Wenge Liu; Yanjin Lu; Tingting Huang; Jinxin Lin (Chemical Engineering Journal, 2026)

Transient receptor potential vanilloid channels in inflammatory bowel diseases: linking inflammation, angiogenesis, and oxidative stress - Peihong Li; Yikun Zhang; Siqing Guo; Hongyi Hu; TingJun Cheng; Kexin Zeng; Tingting Zhang; Linda Zhong; Jiang Lin; Boyun Sun (Inflammopharmacology, 2026)

Dietary protein requirement of juvenile silver pomfret (Pampus argenteus): effects on growth performance, protein utilization, ammonia metabolism, and immune responses - Yini Lin; Xuran Liu; Tingliang Lei; Shunshun Tao; Wenli Zhao; Tingting Zhu; Peng Sun; Óscar Monroig; Juan Carlos Navarro; Qicun Zhou; Min Jin (Aquaculture, 2026)

Polyculture phytoremediation systems enhance tetracycline antibiotic removal and suppress ARG dissemination in plateau lake littoral zones - Hairui Li; Rui Liu; Tingting Dai; Kun Wang; Hua Zhang; Dasong Lin; Qian Li (Journal of Water Process Engineering, 2026)

Thunderstorm activity over Fujian and Vicinity: Insights from thunderstorm tracking technology - Biao Zhu; Binbin Lin; Tingting Chen; Dan Li; Bo Pang; Hengyi Liu (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Expanded coverage of N-acyl amino acids using one-pot micro synthesis-chemical derivatization-LC-MS strategy: A key to bioactive compounds analysis in fermented soybean - Jie Han; Yujie Li; Lanjia Ao; Li Zhang; Tingting Zhou; Na Li; Jian-Lin Wu (Food Chemistry, 2026)

Transforming pallet systems for global shipping decarbonization - Tingting Zhang; Hanmo Wang; Zongguo Wen; Lanxin Zhang; Fan Fei; Alexander Lin; Paul Ekins (Environmental Impact Assessment Review, 2026)

Advanced wick design in solar multistage distillation for on-site water recycling and salt recovery during saline soil remediation - Canjie Lin; Chao Wang; Yang Liu; Changting Wang; Ziwei Liao; Yuyou Lin; Tingting Zheng; Jinjuan Chen; Bolun Peng; Jianping Cao; Bei Liu; Lingyue Zhang; et al. (Chemical Engineering Journal, 2026)

Self-assembling gardenia pectin gel for cholestatic liver injury: Dual mechanisms of hepatoprotection via PPARα activation and gut microbial modulation - Lanjia Ao; Yujie Li; Lingling Zheng; Xiaolin Chen; Haoyuan Zeng; Wen Miao; Shuxian Yang; Tingting Zhou; Na Li; Jian-Lin Wu (Carbohydrate Polymers, 2026)

Cessation of nitrogen addition maintains higher soil organic carbon stability in a subtropical forest acid soil - Quan Li; Tingting Cao; Shuangbo Bi; Mianhai Zheng; Qiqian Wu; Wenjuan Yu; Man Shi; Zhikang Wang; Yuchen Lin; Yakov Kuzyakov; Xinzhang Song (CATENA, 2026)

Novel insights into the short-term impacts of ambient particulate matter pollution on urinary per- and polyfluoroalkyl substances: A perspective panel study - Tingting Jiang; Xin Chou; Yue Shen; Qingxiu Xie; Qunan Wang; Zhijing Lin (Atmospheric Pollution Research, 2026)

Correction: Stem Cell-Derived Exosomes Improve Neurological Dysfunction in a Rat Model of Moderate-to-Severe Cerebral Palsy - Tingting Peng; Huijuan Lin; Xiaoli Zeng; Yunlan Xie; Jie Luo; Lingjie Zhang; Shiya Huang; Zhiyi Ye; Xiaolin Guo; Wen Le; Mingtong Zhang; Wenhui Li; et al. (Stem Cell Reviews and Reports, 2026)

Environmental Factors Drive Neurodegenerative Diseases Through Glutamate Excitotoxicity: A Convergent Mechanistic Pathway - Yulu He; Tingting Yi; Meixin Min; Ke Xu; Huan Lin; Rong Xu; Dan Deng; Xiaoping Xiao (Neuroscience Bulletin, 2026)

Mapping global floodplain development disparities highlights drivers behind intensifying flood losses - Zhiyang Lan; Wenbin Liu; Rafael Jan Pablo Schmitt; Chaoyang Wu; Yingjie Li; Deliang Chen; Peirong Lin; Kailiang Yu; Xinli Bai; Kaihao Zheng; Tingting Wang; Hong Wang; et al. (Science Bulletin, 2026)

Revealing performance and environmental thresholds of mangrove nature-based solutions: A nonlinear blue carbon response framework from coastal Hainan - Kaiyue Wang; Penghua Qiu; Dezhi Wang; Xinqing Zou; Meihuijuan Jiang; Tingting Si; Zhihang Wang; Yi Lin; Yanli Yang; Siang Wan; Yang Li (Journal of Environmental Management, 2026)

Dual-configuration arabinogalactan-II synergizes with rhamnogalacturonan-I in Lycium barbarum pectin to construct an intestinal anti-inflammatory glycan scaffold - Guoqiang Li; Yajun Qiao; Qiannan Wang; Xingfang Zhang; Lin Rong; Lixin Wei; Tingting Gao; Hongtao Bi (Carbohydrate Polymers, 2026)

Uranium occurrence state in coal gangue and study on uranium leaching via chemical mechanical-thermal activation - Shan Li; Jiulong Cui; Lin Ma; Tingting Zheng; Wentao Li; Gen Huang; Jiushuai Deng; Yijun Cao; Junguo Li; Hongxiang Xu; Zechao Huangfu (Process Safety and Environmental Protection, 2026)

SlCNR promotes the lycopene accumulation and reduces abscisic acid content in postharvest tomato fruit - Shuai Zhang; Mingzhe Mang; Di Chen; Liqun Ma; Shiyuan Zhang; Tingting Hu; Lin Yu; Jiankang Cao; Daqi Fu; Benzhong Zhu; Hongliang Zhu; Guiqin Qu (Postharvest Biology and Technology, 2026)

Coordinating carbon and pollution reduction with human settlements in Chinese cities: A key step toward achieving sustainable development goals - Chengxin Lin; Tingting Xu; Huihui Wang; Tian Jing; Yunsong Yang; Siyu Zhang (Journal of Cleaner Production, 2026)

Removal of lead and ammonia via microcapsules-based microbial induced carbonate precipitation (MC-MICP): Performance and mechanism - Zhong-Fei Xue; Chao Xu; Wen-Chieh Cheng; Lin Wang; Liang Xu; Tingting Deng; Xinyu Xu (Chemical Engineering Journal, 2026)

3D-printed porous titanium alloy scaffolds modified with composite hydrogel-loaded emodin liposomes for the treatment of periprosthetic joint infection - Jiamin Li; Jiaying Li; Junkai Hu; Tingting Chen; Tao Lin; Jiahao Pu; Lincong Luo; Wenhua Huang (Chemical Engineering Journal, 2026)

Stem Cell-Derived Exosomes Improve Neurological Dysfunction in a Rat Model of Moderate-to-Severe Cerebral Palsy - Tingting Peng; Huijuan Lin; Xiaoli Zeng; Yunlan Xie; Jie Luo; Lingjie Zhang; Shiya Huang; Zhiyi Ye; Xiaolin Guo; Wen Le; Mingtong Zhang; Wenhui Li; et al. (Stem Cell Reviews and Reports, 2026)

Environmental microbial bioprospecting enabled by a Raman fingerprinting and functional sorting on a microfluidic static droplet array - Guoxia Zheng; Yanwen Liu; Huicheng Chen; Ling Lu; Lin Wang; Tingting Jia; Yunhua Wang (Analytica Chimica Acta, 2026)

Characterization of a new isolate of tomato zonate spot virus from Vaccinium uliginosum L. in China - Yueyan Yin; Tao Lin; Ru Dong; Zhijiao He; Jing Zhong; Liling Zhao; Jiawei He; Ming Ding; Tingting Li (Journal of Plant Pathology, 2026)

Downregulation of miR-194-5p impairs cardiomyocyte proliferation and differentiation through targeting Fign in congenital heart disease - Peishan Liang; Guangli Ren; Jie Zhu; Tingting Zhou; Yahong Chen; Jiangang Lin; Yiqiong Zhang; Xiangmeng Qu (Molecular and Cellular Biochemistry, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Quinoline-driven response and functional remodeling of the anaerobic digestion system - Tingting Cui; Chunhui Zhang; Siqi Liang; Zhao Zhang; Liwei Wang; Xinxin Zhang; Leyi Chen; Zepeng Wang; Zhiwei Lin; Yanxin Li; Peidong Su (Journal of Environmental Chemical Engineering, 2026)

Peimisine-sulfide improves inflammation caused by copper sulfate through inhibiting ferroptosis using zebrafish embryos - Siyu Chen; Junyu Liang; Tingting Lin; Zitong Huang; Leyan Huang; Liang Bu; Chuanzhi Kang; Chengyong He (Journal of Environmental Sciences, 2026)

Differential hydroclimatic impacts on prehistoric cultures in the mountain and basin settings of the Minjiang River, Southwest China - Yongxiu Lu; Zhengxuan Gao; Fengyan Lu; Tingting Yan; Jixiao Wang; Yuanxin Li; Qili Xiao; Lin Wang; Liangcheng Tan; Shugang Kang; Guanghui Dong (Global and Planetary Change, 2026)

Unraveling geographical heterogeneity and spatial distribution of Long pepper fruits: An integrative analytical perspective - Shuwen Geng; Conghui Duan; Ying Ye; Yuye Gao; Yujia Zhai; Fangyuan Gao; Yuewei Ge; Yang Chen; Yunxia Li; Rongping Zhang; Xinglong Chen; Jian-lin Wu; et al. (Food Chemistry, 2026)

Multi-membrane integrated process enables efficient electrodialytic separation of alkaloids from aqueous extract of Caulis sinomenii - Lanlan Zhang; Xixi Ma; Tingting Xu; Shanshan Liu; Luna Chen; Jiaming Ji; Jinfeng He; Li Sun; Xiaocheng Lin; Chuanrun Li; Haiyang Yan (Desalination, 2026)

Review: Synergistic effects of environmental pollutants: Multiple stressors driving the transmission of vector-borne diseases and the vicious cycle - Tingting Liu; Jia Wang; Minghao Yu; Yining Li; Huan Lin; Dan Deng; Xiaolu Shi; Xiaoping Xiao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Eco-Friendly Dust Control Strategies: A Critical Review of Chemical Suppressants for Sustainable Environmental Management - Nini Wang; Zhihui Huang; Lin Yang; Tingting Han; Nan Wang; Xiangpeng Meng; Wei Zhang (Water, Air, & Soil Pollution, 2026)

Performance of Wetland in Pollutant Removal: a Review - Yifan Zhuo; Sangar Khan; Wenting Liu; Tingting Hu; Yuke Duan; Zongwei Lin; Xinxin Qi; Collins Oduro; Hongli Mu; Naicheng Wu (Water, Air, & Soil Pollution, 2026)

Nondecomposer-mediated nutrient transfer in soils: experimental evidence from Drosophila - Yunchao Luo; Run Liu; Tingting Cao; Jiayue Zhang; Mengna Zhao; Ke Li; Zunian Ran; Lin Wang; Xingjun Tian (Applied Soil Ecology, 2026)

Bisphenols and parabens in soils and outdoor dust from a metropolitan city in the Guangdong–Hong Kong–Macao Greater Bay Area, China: concentrations and human exposure risk - Xulong Chen; Xiujuan Qi; Bingjun Lu; Yuli Lin; Bo Fu; Chiqun Shan; Xiangxuan Kong; Kai Lin; Tingting Zhu; Shaoyou Lu (Environmental Monitoring and Assessment, 2026)

Improved swimming performance from exercise training is driven by optimized muscle energy metabolism and antioxidant capacity in juvenile large yellow croaker Larimichthys crocea - Sijian Deng; Yuhe Yang; Tingting Lin; Xin Liu; Yazhou Jiang; Zhengli Fang; Siping Li (Aquaculture, 2026)

Degassing in middle-crust magma chamber: Evidence from the texture and chemistry of the zonal clinopyroxene from the high magnesium basalt in Ganzhou Basin, Jiangxi, South China - Lin Jia; Guolin Guo; Yan Zhao; Zhaobin Yan; Jianhua Wu; Wenya Yan; Tingting Zou (Geochemistry, 2026)

Study on the structure-activity relationship and effect evaluation of benzo -γ -pyrones anti-S. aureus Hla inhibitors - Tingting Sun; Lin Jiang; Lijiao Yang; Siyi Chen; Yang Liu; Jing Liu; Fei Xu (Food Bioscience, 2026)

Highland barley arabinoxylans with distinct molecular features modulate retrogradation and in vitro digestibility of highland barley starch - Yonghui Dong; Tingting Mu; Xue Wu; Chunping Chen; Haiyu Wu; Lin Han; Caian He; Min Wang (Food Hydrocolloids, 2026)

Microplastics found in Weddell seal placenta in Antarctica, potential threatening marine ecosystem health - Xing Miao; Conghui Peng; Renxin Zhang; Baohong Chen; Zongzheng Chen; Hui Lin; Tingting Fu; Yuan Li; Longshan Lin (Journal of Hazardous Materials, 2026)

Pyrolysis atmosphere dictates the efficacy of peanut shell biochar in promoting anaerobic digestion of chicken manure - Tingting Zhang; Xiaohong Su; Xinrui Xu; Ruian Lin; Hongmei You; Yupeng Wang; Chuang Zhou (Journal of Environmental Chemical Engineering, 2026)

Occurrence, distribution, and potential risk of per- and polyfluoroalkyl substances in soil, outdoor dust, and atmospheric particles in the electronic industrial agglomeration zone in South China - Hanying Zheng; Xulong Chen; Bingjun Lu; Pei Luo; Bei Wang; Chiqun Shan; Bo Fu; Yuli Lin; Muchen Yin; Jiayi Xu; Xiangxuan Kong; Tingting Zhu; et al. (Environmental Pollution, 2026)

Spectral-diagonalization-based matrix exponential integration for efficient and stable solutions of full-Bloch equations in surface NMR - Tingting Lin; Qingyue Wang; Chuandong Jiang; Chunpeng Ren; Yunzhi Wang; Liang Wang (Computers & Geosciences, 2026)

Ternary deep eutectic solvents as multifunctional green solvents for lignocellulosic biomass pretreatment - Thenapakiam Sathasivam; Tingting Wu; Udyani Aloka Weerasinghe; Pek Yin Michelle Yew; Xin Lin Quek; Yi Jie Eng; Dan Kai (Bioresource Technology, 2026)

A warming and wetting climate increases the width and intensity of braided channels in the Yangtze River source region: a case study of the Beilu River - Qianyue Guo; Tingting Jiang; Jinpo Li; Zhipeng Lin; Yuqi Shan; Chao Liu (Environmental Fluid Mechanics, 2026)

Regulatory mechanisms underlying stress-induced accumulation of plant secondary metabolites - Sujing He; Jiangna Wang; Ning Yang; Hongwei Li; Kunqian Li; Lin Li; Wei’e Wen; Tingting Luo; Juanjuan Zhao; Delin Xu (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Controllable oxidase-mimic activity of magnetic Fe3O4@metal-organic framework core-shell heterogeneous nanozyme aroused by chlorpyrifos for monitoring chlorpyrifos residue in foods and bioaccumulation in rice - Lin Zhou; Guanghao Chen; Tingting Cai; Jie Tang; Jintong Liu; Hong Yang (Food Chemistry, 2026)

Smartphone-assisted sensing array based on covalent organic framework-enhanced AuPtPd hybrid oxidase-mimic nanozyme for controllable quantitative detection of acephate residue and bioaccumulation in wheat - Tingting Cai; Guanghao Chen; Lin Zhou; Jie Tang; Jintong Liu; Hong Yang (Chemical Engineering Journal, 2026)

Transcriptomic analysis reveals the toxic effects of Clothianidin on the embryonic development of zebrafish - Tingting Qian; Zhonghua Fan; Xiyue Liu; Ying Yang; Lin Cheng; Zhou Zhou; Ziheng Xiao; Lijuan Yuan; Li Wang; Hui Liu (Toxicology and Applied Pharmacology, 2025)

Elevated blood microplastics and their potential association with Parkinson’s disease - Zongtang Xu; Xingting Huang; Ziting Zhu; Fengchu Liang; Huimin Hu; Tingting Cai; Tianni Liu; Weiqing Huang; Lin Lu; Pingyi Xu; Wenlong Zhang (Journal of Hazardous Materials, 2025)

Confinement engineering of Co@C nanocages in 3D g-C3N4 scaffolds boosts photothermal CO2-to-fuel conversion - Yanan Wang; Jingjie Li; Rui Zhang; Tingting Xu; Chenlu Li; Jie Ma; Han Li; Liwei Lin; Song Xu; Man Zhou; Zhongyu Li (Journal of Environmental Chemical Engineering, 2025)

Rational design of molybdenum carbide loaded Fe3O4 for rapid and repeated water disinfection: Photothermal effect and bactericidal mechanisms - Tingting Jiang; Sihui Bian; Siyu Huang; Guanbo Wang; Xinyue Song; Lin Zhu (Journal of Environmental Chemical Engineering, 2025)

Mechanism of piezoelectric field-enhanced electron transfer during peroxymonosulfate activation with MoS2/PVDF-HFP films - Tingting Cao; Liping Lin; Yanan Li; Wangshu Tong (Journal of Environmental Chemical Engineering, 2025)

Optimizing MERRA-2 aerosol extinction coefficient by fusing CALIPSO and SAGE observations with machine learning - Jingru Yang; Lin Zang; Feiyue Mao; Yi Zhang; Weiwei Xu; Fan Liu; Tingting Liu (Atmospheric Environment, 2025)

Transcription factor VlPAT2 enhances the resistance of grapevine to Botrytis cinerea by promoting ROS accumulation - Xiangyu Zhou; Tingting Du; Xiaolele Ma; Xiaoli Zhang; Yanqiu Du; Xiao Liang; Songlin Zhou; Wenhao Wang; Hong Lin; Changyue Jiang; Yinshan Guo (Plant Cell Reports, 2025)

Seasonal water level fluctuations regulate the source, distribution, and risk of antibiotics in the largest floodplain-lake in China - Xiaolong Huang; Cong Wang; Yiting Chen; Meng Zhang; Muhammad Zaffar Hashmi; Tingting Sun; Borui Zou; Yuanyan Zhang; Jingjing Lin; Zhi Wang (Water Research, 2025)

Source apportionment of environmentally persistent free radicals in size-resolved PM: Implications for driving oxidative potential and reactive oxygen species generation - Fanyi Wei; Sutong Wang; Yihan Guo; Lixian Lin; Tingting Xu; Huibin Guo (Journal of Hazardous Materials, 2025)

Imidazolium-carboxylate ionic liquids as latent curing agents for epoxy resin with excellent storage, thermal stability, and mechanical properties - Chen Tan; Ziqing Liang; Tingting Xiao; Gary Histand; Dongen Lin (Chemical Engineering Journal, 2025)

An SENet-enhanced transformer approach for multi-condition fast forecasting of two-phase bubble flows - Leqi Lin; Yang Liu; Tingting Liu; Ming Pan; Xizhong Chen (Chemical Engineering Journal, 2025)

Deep eutectic solvent-assisted 3D printing of lignocellulosic biomass - Tingting Wu; Sigit Sugiarto; Udyani Aloka Weerasinghe; Ruochen Yang; Linran Jia; Pek Yin Michelle Yew; Danwei Zhang; Thenapakiam Sathasivam; Pei Lin Chee; Xunchang Fei; Dan Kai (Chemical Engineering Journal, 2025)

Effects of undergrazing and ferterlizer addition management on community assembly and stability of Horqin sandy grasslands - Litao Lin; Haiguang Hao; Chao Zhang; Bitao Feng; Qin Qiao; Tingting Sun (Journal of Environmental Management, 2025)

Efficient utilization of low-grade ilmenite: An innovative approach integrating pre-oxidation with CH₄-H₂ direct reduction for titanium carbide production - Tingting Lv; Jianwei Song; Yunfei An; Tu Hu; Guo Lin; Baocheng Zhou (Journal of Environmental Chemical Engineering, 2025)

Long-term effectiveness evaluation of Cr(VI)-contaminated soil remediation with modified iron-biochar composites - Lihong Xie; Yi Zhou; Qiyan Ma; Jinlan Zhang; Guilan Duan; Aijun Lin; Yong Xiao; Tingting Zhang (Journal of Environmental Chemical Engineering, 2025)

Engineered biochar amended co-composting for greenhouse gas mitigation, nitrogen conservation, and eco-efficiency assessment - Yanyan Huang; Xu Yang; Jianhong Li; Hailong Wang; Hongzhu Yang; Tingting Yang; Dongming Zhang; Xianghui Zhang; Wenhui Lin; Caiwang Cheng; Paramsothy Jeyakumar; Ronghua Li; et al. (Journal of Environmental Chemical Engineering, 2025)

Developmental exposure to echimidine induces locomotor hyperactivity in zebrafish larvae via inhibiting acetylcholinesterase activity - Tingting Lin; Siyu Chen; Yingyi Ren; Junyu Liang; Zhenghong Zuo; Zhiqiang Luo; Jian Yang; Chengyong He (Journal of Environmental Sciences, 2025)

Sources, temporal-spatial characteristics, exposure assessment and children health risk of phthalate esters (PAEs) in household dust in China from 2000 to 2023: a review and pool analysis - Wenying Zhang; Xiaotong Zhang; Xiaomin Xie; Tingting Liu; Fengjing Song; Chengyu Chen; Chao Wang; Linlin Jiang; Hang Du; Lin Fan; Xu Han; Yiming Sun; et al. (Environmental Pollution, 2025)

Low-intensity pulsed ultrasound enhances delivery of 30 nm Q10 for improving mental and memory disorder in APP/PS1 mice - Qi Luo; Xuanjie Ye; Jinan Xu; Zihui Sun; Panpan Wang; Haishu Chen; Tingting Gao; Qiangfeng Deng; Ziwen Wang; Qin Wang; Xiaoxiao Chen; Zhuowen Zhao; et al. (Drug Delivery and Translational Research, 2025)

Characterizing Gray matter atrophy patterns associated with accelerometer-measured sedentary behavior: a population-based study - Minle Tian; Xiaolei Han; Ming Mao; Xiaomeng Li; Yi Dong; Jiahao Ding; Qinghua Zhang; Shi Tang; Xiaojuan Han; Lin Song; Tingting Hou; Lin Cong; et al. (Brain Imaging and Behavior, 2025)
Evidence has linked self-reported sedentary behaviors with dementia and cognitive impairment; however, the underlying mechanisms remain poorly understood. We investigated the associations of accelerometer-measured sedentary behavior patterns with gray matter atrophy patterns in rural-dwelling older adults, while taking into account the manner in which sedentary time is accrued (in short or long bouts). This community-based study involved 911 dementia-free older adults (age ≥ 60 years, 59% women) who participated in both ActiGraph and brain MRI substudies within MIND-China (2018–2020). Sedentary behavior parameters (total sedentary time, mean sedentary bout duration, and sedentary breaks) were recorded with accelerometers. Regional gray matter volumes (GMV) were measured using voxel-based morphometry (VBM) methods. Data were analyzed using the general linear regression models, restricted cubic spline curves, and VBM analysis. There was an inverted U-shaped association between daily sedentary time and GMV in temporal, cingulate, and medial temporal cortex, while longer mean sedentary bout duration was linearly related to decreased GMV in total, frontal, temporal, insula, cingulate, and medial temporal cortex. Greater daily time spent in light or moderate-to-vigorous physical activity (LPA and MVPA) was correlated with larger insula GMV. The VBM analysis suggested that prolonged daily total sedentary time and mean sedentary bout duration were significantly associated with smaller GMV in extensive brain regions, especially in thalamus and insula. In conclusion, gray matter atrophy associated with sedentary behavior in older adults is characterized by reduced GMV in global, frontal, temporal, medial temporal, and cingulate cortex, especially in the insula and thalamus regions.

A Large Bioenergy Potential from the Third-Generation Bioenergy Crop Microalgae on Abandoned Croplands in China - Peng Cheng; Fengsong Pei; Tingting Kang; Junjie Wang; Kuiqi Yang; Lin Mao (BioEnergy Research, 2025)

Dielectrically optimized Ni/CeO2/CNT catalysts for low-power and stable microwave-assisted dry reforming of methane - Tingting Wang; Xiaojun Li; Fengjuan Liu; Bei Liu; Xinkang Peng; Zhiheng Wang; Ning Qu; Jie Kong; Zhenchen Tang; Feng Zeng; Han Lin; Xiaohua Lu; et al. (Chemical Engineering Journal, 2025)

Nanozyme meets pathogen: A M-MXene@CuS platform for triple-mode detection and synergistic inactivation of MRSA - Tingting Su; Yingming Zhang; Yuting Chang; Xianfeng Lin; Meihua Dong; Shijia Wu; Zhouping Wang; Nuo Duan (Chemical Engineering Journal, 2025)

Atomically dispersed noble metal-Ox sites for electrocatalytic chlorine evolution - Chen Chen; Baoyi Guo; Tingting Liu; Ruting Lin; Yuyu Liu; Qiufeng Huang; Xiaofeng Zhang; Jiabao Huang; Fangren Qian; Shengyun Huang; Qingjun Chen; Xueqin Mu; et al. (Chemical Engineering Journal, 2025)

Cellulose nanocrystal-modified hydrogel wearable sensor with self-healing function from dynamic bond and controllable dual hydrogen-bond crosslinking - Ruihuan Gu; Weiwei Chen; Yanrui Zou; Tingting Yang; Zirui Liu; Ning Yu; Jin Huang; Lin Gan (Carbohydrate Polymers, 2025)

Magnesium isotope compositions of seep carbonates fingerprint dolomite formation pathways - Tingting Chen; Yang Lu; Zhiyong Lin; Wei Wei; Xiaoming Sun; Fang Huang (Chemical Geology, 2025)

Assessment of spatial and temporal variability in fecal contamination patterns within urbanized bay shellfish growing area utilizing community-based microbial source tracking approaches - Jiannan Lin; Hongxia Ming; Dongwei Li; Jiajie Li; Zhongzhi Chen; Ziqi Chen; Tingting Shi; Jie Su; Jingfeng Fan (Environmental Monitoring and Assessment, 2025)

Per- and polyfluoroalkyl substances mixture impairs intestinal barrier function through microbiota-derived 21-deoxycortisol and cortisol metabolism dysregulation - Tingting Lin; Luyang He; Sishuo Liu; Yahui Li; Zhi Huang; Delei Cai; Yiming Wang; Zhe Mo; Yi Zhu; Zhijian Chen; Peiwei Xu; Xiaoming Lou; et al. (Journal of Hazardous Materials, 2025)

Unveiling the components, physiological functions and emerging trends of hydroxycinnamic acid amides in goji berry (Lycium) - Siyuan Wei; Yuying Wang; Shiyu Zhou; Shina Luo; Yunuo Lin; Ruixi Wang; Qinyue Jia; Tingting Feng; Guoping Zhao; Xuefeng Yin; Fangwei Yang (Food Research International, 2025)

Revolutionary photoelectrochemical water splitting performance of BiVO₄/Bi₂S₃ heterojunction photoanodes boosted by trace bio-Cr₂O₃ through multiple mechanisms - Yefei Su; Yang Yu; Tingting Xue; Kai Teng; Yuning Fan; Jiangjun Lin; Chang Liu; Qing Qu; Lei Li (Chemical Engineering Journal, 2025)

MiR-223-3p inhibits hippocampal neurons injury and exerts anti- anxiety/depression-like behaviors by directly targeting NLRP3 - Wenyuan Wang; Tingting Yang; Na Liu; Lin Yang; Cong Liu; Xiaoxiao Qi; Ning Wang; Mingwei Wang; Yanyong Wang (Psychopharmacology, 2025)

Application of artificial intelligence in the rapid determination of moisture content in medicine food homology substances - Mengyu Zhang; Boran Lin; Shudi Zhang; Cheng Peng; Chang Li; Tingting Feng; Lian Li; Aoli Wu; Chunguo Yang; Wentian Wang; Shouyao Huang; Lei Nie; et al. (Food Chemistry, 2025)

SIRT1 Regulates Iron Metabolism to Attenuate β-Cell Dedifferentiation by Inhibiting FoxO1 Acetylation - Tingting Li; Rulin Ma; Wennv Tang; Yanxia Zheng; Siyi Lv; Yuxi Liu; Lin Wang; Yusong Ding (Biological Trace Element Research, 2025)

The AHL-driven cascade of rhizosphere microbes, enzymes, and nutrients contributes to the growth decline of Casuarina equisetifolia in continuous planting systems - Qingxu Zhang; Yi Lin; Lei Hong; Yuhua Wang; Miaoen Qiu; Jianjuan Li; Tingting Wang; Zongnan Wu; Mingmei Wu; Wenxiong Lin; Haibin Wang; Zeyan Wu (Rhizosphere, 2025)

A halloysite nanotubes-based hybrid fluorous monolith as the mixed-mode sorbent for hydrophilic and hydrophobic interactions and its application for analysis of antibiotics from milk powder and milk samples - Cheng Lin; Jiarun Mao; Yihui Chen; Chunyan Hou; Xiaoqiang Qiao; Ningkun Wu; Tingting Wang (Food Chemistry, 2025)

Composite antimicrobial films activated by essential oil pickering emulsions: Preparation, characterization and application in pork preservation - Lin Liu; Tanghui Liu; Guihong Li; Qingqing Tan; Anjun Tang; TingTing Wen; Ziming Li; Hai Chi; Hongrui Chen; Jie Tang; Xingzhong Zhang (Food Bioscience, 2025)

Characterization and gelling properties of pectin extracted from Gardenia fruit - Xuan Wang; Tian Tian; Na Li; Lingling Zheng; Yuyao Wu; Wei Bian; Jian-Lin Wu; Tingting Zhou (Food Hydrocolloids, 2025)

Characterizing ancient seep environments by in-situ sulfur isotope composition of authigenic pyrite - Qinyi Zhang; Zhiyong Lin; Harald Strauss; Tingting Chen; Yang Lu; James L. Goedert; Jörn Peckmann (Chemical Geology, 2025)

GLA deficiency causes cardiac hypertrophy via enhanced autophagy - Wei Ou; Xi Li; Kuo Tang; Lin Ding; Tingting Sun; Qian Li; Tao Li (Science China Life Sciences, 2025)

Associated effects of blood metal(loid) exposure and impaired glucose metabolism in patients with gastric precancerous lesions or gastric cancer - Yuting Zhu; Xiao Lin; Tingting Wang; Sheng Wang; Wuqi Wang; Mengran Ke; Yan Zhu; Bowen Zhang; Princess Ofosuhemaa; Yalei Wang; Mingjun Hu; Wanshui Yang; et al. (BioMetals, 2025)

Comprehensive analysis of microplastics at typical outlets around Hainan Island: From spatial distribution to flux estimation and correlation analysis - Shiyu Xie; Yuanyuan Su; Dan Qi; Fei Liu; Liu Gao; Ruiqi Bao; Xing Cheng; Xubing Lin; Tingting Zhang; Licheng Peng (Water Research, 2025)

Changing patterns of tailings physicochemical properties, community structure, and functional genes during cadmium biomineralization in tailings by carbonate-mineralized bacteria - Lili Zheng; Tingting Yin; Yanrong Lu; Hai Lin; Yingbo Dong (Process Safety and Environmental Protection, 2025)

Enhancing mycophenolic acid production in Penicillium brevicompactum through Kozak-optimized 2A peptide multi-gene expression system - Jishou Wu; TingTing Hu; Lin Lin; Yan Yan; Tao Li; Wei Wei; Dongzhi Wei (Fungal Biology, 2025)

Faraday cage-type photocurrent polarity switching photoelectrochemical sensing platform for highly selective and sensitive detection of Vibrio parahaemolyticus - Qingqing Zhang; Tingting Zhai; Yuxin Guo; Yifan Weng; Nan Zhou; Han Lin; Hao Tan; Kangning Lu; Yiyi Zhou (Food Chemistry, 2025)

Extracellular polymers substances towards the toxicity effect of Microcystis flos-aquae under subjected to nanoplastic stress - Jianhuang Su; Jiahui Lin; Wenlu Zhan; Jianjie Li; Xiuxian Dong; Tingting Zhang; Zaixian Yang; Zhuanxi Luo; Peiyong Guo (Environmental Pollution, 2025)

Blue carbon potential from rehabilitating urban mangrove forests in coastal city - Peiyang Qiao; Yue Meng; Changxin Liu; Tingting Zhang; Mei Li; Liangxia Feng; Qinchang Chen; Jialin Zhang; Chen Lin; Xiaoxuan Gu; Luzhen Chen (Estuarine, Coastal and Shelf Science, 2025)

Perovskite quantum dots Revolutionize Lithium-Sulfur battery Performance: Cathode catalytic Breakthrough with CsPbBr3 - Renjing Duan; Xiaoshi Lang; Xiang Wang; Lan Li; Tingting Qu; Lin Wang; Jianbin Li; Chuangang Yao; Kedi Cai (Chemical Engineering Journal, 2025)

Embracing Internal States: A Review of Optimization of Repetitive Transcranial Magnetic Stimulation for Treating Depression - Tingting Wu; Qiuxuan Yu; Ximei Zhu; Yinjiao Li; Mingyue Zhang; Jiahui Deng; Lin Lu (Neuroscience Bulletin, 2025)

Impact of Faba Bean (Vicia faba L.) Diet and Subsequent Withdrawal on GIFT Tilapia (Oreochromis niloticus) Muscle Quality - Guanling Xu; Wei Xing; Tieliang Li; Shibo Wei; Ying Zhang; Tingting Song; Huanhuan Yu; Lin Luo (Fishes, 2025)
To systematically evaluate FB’s effects on tilapia muscle quality, two distinct experimental phases are designed, the crispy texture development phase (0–16 weeks) and the crispy texture retention phase (17–24 weeks), which can determine the minimum faba bean (FB) feeding duration required to achieve optimal textural modification and can assess the persistence of improved textural properties following FB withdrawal, respectively. The results demonstrated that a 60% FB inclusion diet administered for 16 weeks did not adversely affect tilapia growth performance. Significant improvements in textural parameters, including hardness, springiness, chewiness, and shear force, were observed in FB-fed tilapia as early as 8 weeks, with these enhancements being maintained throughout the 16-week feeding period. These superior textural characteristics persisted during the subsequent retention phase following FB withdrawal. Microstructural analysis revealed that the 60% FB diet significantly enhanced muscle-fiber density while reducing fiber diameter in tilapia during the 8–16 week feeding period. These microstructural modifications persisted throughout the texture retention phase, maintaining significant differences compared to the control group. Serological analysis demonstrated the FB group elevated Superoxide dismutase (SOD) activity and reduced malondialdehyde (MDA) levels at 4 weeks, though these differences normalized thereafter. qRT-PCR showed the 60% FB clearly increased the expression of mstn at 8 weeks, while col1a-2 and myog expressions also obviously improved at 12 weeks. In summary, dietary 60% FB improved tilapia muscle crispiness by altering texture and microstructure via gene-expression regulation. The minimum duration was 8 weeks to achieve crispiness in tilapia by the 60% FB diet without adverse effects on growth, immunity, and hepatopancreas function. Furthermore, the crispy texture of tilapia fillets was maintained for at least 2 months following withdrawal of the 60% FB diet after 16 weeks of continuous feeding.

Boosting catalytic performance of N doped porous carbon derived from coal tar pitch: The role of N species and the contribution of 1O2 - Linlin Huang; Xuwen Zhang; Lin Wang; Tingting Liu; Da Li; Tao Sheng; Caiyu Sun; Lixin Li (Journal of Water Process Engineering, 2025)

Spatial metabolomics and feature-based molecular networking to unveiling in-situ quality markers landscape and reflecting geographic origins of pomegranate seeds - Yuye Gao; Tian Tian; Xiaojing Liu; Yi Zhang; Ping Hai; Wei Zhang; Yujia Zhai; Chen Wang; Jian-lin Wu; Jun Wen; Tingting Zhou (Food Chemistry, 2025)

Mussel-inspired integrated functional 3D printed scaffolds with molybdenum disulfide nanoflowers for tumor therapy and bone reconstruction - Lan Li; Rongcan Wu; Ruchen Hong; Xiaolong Chen; Tingting Huang; Siyi Huang; Xianglei Mo; Zhiyi Wang; Wenge Liu; Yanjin Lu; Ye Wu; Jinxin Lin (Chemical Engineering Journal, 2025)

Three new anti-inflammatory stilbenoids and a diphenyl ether derivative from Cajanus cajan - Liyuan Yao; Xiaobao Huang; Tingting Lin; Sheng-Xiang Qiu (Natural Product Research, 2025)

ETV5-Mediated Transcriptional Repression of DDIT4 Blocks Macrophage Pro-Inflammatory Activation in Diabetic Atherosclerosis - Lili Shi; Tingting Sun; Di Huo; Lin Geng; Chao Zhao; Wenbo Xia (Cardiovascular Toxicology, 2025)

Controlling verticillium wilt in Acer mollo maxim with a star polycation dsRNA delivery system targeting Verticillium dahliae VDAG_03333 - Yuan Tao; Tingli Liu; Lingchao Cai; Chaoqun You; Hanchen Lin; Yufang Guo; Tingting Dai (Journal of Cleaner Production, 2025)

Mechanism and application of environmental engineering and civil engineering: From biological nanoarchitectonics to system engineering - Peidong Su; Meiguangzi Guo; Qing Wen; Xiaoping Zhong; Zaining Li; Tingting Cui; Chunhui Zhang; Junke Zhang; Wentao Jiao; Lin Li (Journal of Environmental Chemical Engineering, 2025)

Engineered silicon-titania heterojunction elicits catalytic cancer cell death - Deliang Xu; Tingting Xu; Min Ge; Shibo Cao; Zhaoda Yu; Zhixin Chen; Ya-Xuan Zhu; Zhuang Liu; Ming Zong; Han Lin; Jianlin Shi (Chemical Engineering Journal, 2025)

Freshness Prediction of Silver Carp Using Sub-Layer Equivalent Circuit Parameters in Electrochemical Impedance Spectroscopy - Jian Sun; Ruiting Xia; Feng Lin; Kai Wu; Jinfu Chen; Gangshan Wu; Wei Pan; Tingting Zou (Journal of Aquatic Food Product Technology, 2025)

Salicylic acid treatment improves the storability of fresh longan by regulating the metabolisms of respiration and energy - Huili Zhang; Tingting Shan; Yang Chen; Hongyi Wen; Mengshi Lin; Zhongqi Fan; Hui Wang; Yihui Chen; Hetong Lin; Yifen Lin (Postharvest Biology and Technology, 2025)

Geochemical study of UHP serpentinites in southwestern Tianshan, China and its implications for trace elements deep recycling - Tingting Shen; José Alberto Padrón-Navarta; Thomas Bader; Congcong Lin; Tian Qiu; Jingsui Yang (Lithos, 2025)

Study on multi-agent evolutionary games promoting “distributed photovoltaics and electric heating” in rural areas: A case study in Xi'an, China, a pilot city for clean heating - Jianghua Liu; Xi Luo; Xiaojun Liu; Yaru Gao; Tingting Zhou; Xiongxiong Zhai; Lin He (Journal of Cleaner Production, 2025)

Efficient remediation of different concentrations of Cr-contaminated soils by nano zero-valent iron modified with carboxymethyl cellulose and biochar - Lihong Xie; Qiyan Ma; Qingjun Chen; Yiyang Liu; Pengfei Guo; Jinlan Zhang; Guilan Duan; Aijun Lin; Tingting Zhang; Shangyi Li (Journal of Environmental Sciences, 2025)

Three-mode ratiometric biosensor based on integrated DNA-driven magnetic beads for Clostridium perfringens detection - Wenzhuo Wang; Wei Yuan; Tingting Lin; Zhilan Sun; Fei Liu; Daoying Wang; Fang Liu (Food Chemistry, 2025)

Effect of hot-air drying processing on the volatile organic compounds and maillard precursors of Dictyophora Rubrovalvata based on GC-IMS, HPLC and LC-MS - Lingshuai Meng; Yu Nie; Qingsong Zhou; Tingting Zheng; Jianxin Song; Chao Zhang; Haijiang Chen; Dong Lin; Sen Cao; Su Xu (Food Chemistry, 2025)

Factors influencing K-struvite purity via phosphorus coprecipitation in synthetic urine: Verification, quantification, and modelling - Lin Wei; Yiming Tang; Tingting Zhang; Junjie Ji; Qiang Zhang; Yugang Dong; Lei Luo; Xiaoke Ding; Jianyu kong (Environmental Research, 2025)

Enhancing electromechanical conversion and motion-monitoring application of pore-oriented cellulose nanocrystal/agarose aerogel modified with flexible heterojunction structures - Weiwei Chen; Lin Gan; Jie Xiong; Ga Liu; Tingting Yang; Yanrui Zou; Zhicheng Zhang; Jin Huang (Carbohydrate Polymers, 2025)

Supplementation with probiotics co-cultivation improves the reproductive performance in a sow-piglet model by mother-infant microbiota transmission and placental mTOR signaling - Suchen Li; Tingting Lu; Zhixin Lin; Yuanyuan Zhang; Xinchen Zhou; Meng Li; Hui Miao; Zhiren Yang; Xinyan Han (World Journal of Microbiology and Biotechnology, 2025)

Mitigation of cadmium and arsenic in rice grain by zero valent iron through modifying the soil chemical property and microbial community structure - Tingting Li; Dasong Lin; Chao Liu; Junhui Zhang; Yuefeng Yu; Fuhai Zheng; Junming Hu (Plant and Soil, 2025)

Molecular Regulatory Mechanism of Nano-Se Against Copper-Induced Spermatogenesis Disorder - Yujuan Ouyang; Yanbing Lou; Yanqiu Zhu; Yihan Wang; Song Zhu; Lin Jing; Tingting Yang; Hengmin Cui; Huidan Deng; Zhicai Zuo; Jing Fang; Hongrui Guo (Biological Trace Element Research, 2025)

Effects of thermal oxidation interaction via various polar lipid and myofibrillar proteins on the aroma formation in large yellow croaker - Tingting Zhang; Ke Zhang; Xinyi Qi; Sijia Lin; Lei Qin; Xuhui Huang (Food Bioscience, 2024)

The roles of organic amendments and plant treatments in soil polychlorinated biphenyl dissipation under oxic and sequential anoxic–oxic conditions - Meng Yan; Tingting Peng; Ling Zhao; Qigang Li; Ruini Wu; Yiming Wang; Yucheng Wu; Ying Teng; Xingjia Xiang; Jun Zeng; Xiangui Lin (Environmental Research, 2024)

Application of bio-based nanopesticides for pine surface retention and penetration, enabling effective control of pine wood nematodes - Hanchen Lin; Like Ning; Tingting Dai; Wei Wei; Ning Ma; Mei Hong; Fei Wang; Chaoqun You (Chemical Engineering Journal, 2024)

Metal-organic framework-sealed heterogeneous nanoenzyme: A dual-mode core–shell sensor for sensitive determination of the chlorpyrifos residue in environment and bioaccumulation in food - Jintong Liu; Jie Tang; Yanyang Mo; Lin Zhou; Tingting Cai; Hong Yang (Chemical Engineering Journal, 2024)

Enhanced nitrogen and phosphorus removal from mariculture water using immobilized bacteria and macroalgae - Tingting Ye; Min Li; Yuanbin Lin; Bingtao Wei; Zengjian Su (Journal of Environmental Management, 2024)

Heteronuclear FeN3-CuN3 atom pairs coordination engineering of single-atom catalysts for water splitting and Zn-Air batteries - Yinglin Zhang; Bo Yan; Chenchen Ji; Tingting Wei; Wenbin Niu; He Lin; Yulin Shi (Chemical Engineering Journal, 2024)

The nexus of solar absorption and morphology designs based on 2D photothermal materials: From rational design to advanced application of water purification - Tingting Jiang; Sihui Bian; Yu Wang; Xiaorui Fan; Lin Zhu; Xinyue Song; Guanbo wang; Tianhao Wang; Haifeng Zhang (Chemical Engineering Journal, 2024)

Hybrid 2D/3D carbon framework confined Si with optimized reaction kinetics for highly stable Li-Ion storage - LiLin Lin; Peijun Zhou; Wen Xiong; Tingting Zhao; Shengsong Li; Liangui Yang; Tao Meng; Junhao Zhong; Zhibiao Cui; Dong Shu (Chemical Engineering Journal, 2024)

Soil microbial influences over coexistence potential in multispecies plant communities in a subtropical forest - Weitao Wang; Hangyu Wu; Tingting Wu; Zijing Luo; Wei Lin; Hanlun Liu; Junli Xiao; Wenqi Luo; Yuanzhi Li; Youshi Wang; Chuliang Song; Gaurav Kandlikar; et al. (Ecology, 2024)
Soil microbes have long been recognized to substantially affect the coexistence of pairwise plant species across terrestrial ecosystems. However, projecting their impacts on the coexistence of multispecies plant systems remains a pressing challenge. To address this challenge, we conducted a greenhouse experiment with 540 seedlings of five tree species in a subtropical forest in China and evaluated microbial effects on multispecies coexistence using the structural method, which quantifies how the structure of species interactions influences the likelihood for multiple species to persist. Specifically, we grew seedlings alone or with competitors in different microbial contexts and fitted individual biomass to a population dynamic model to calculate intra‐ and interspecific interaction strength with and without soil microbes. We then used these interaction structures to calculate two metrics of multispecies coexistence, structural niche differences (which promote coexistence) and structural fitness differences (which drive exclusion), for all possible communities comprising two to five plant species. We found that soil microbes generally increased both the structural niche and fitness differences across all communities, with a much stronger effect on structural fitness differences. A further examination of functional traits between plant species pairs found that trait differences are stronger predictors of structural niche differences than of structural fitness differences, and that soil microbes have the potential to change trait‐mediated plant interactions. Our findings underscore that soil microbes strongly influence the coexistence of multispecies plant systems, and also add to the experimental evidence that the influence is more on fitness differences rather than on niche differences.

Differences in the uptake and translocation of differentially charged microplastics by the taproot and lateral root of mangroves - Yichun Lin; Luya Wang; Bigui Lin; Beibei Liu; Tingting Guan; Shuai Guo; Qinfen Li; Chaoxian Wei (Science of The Total Environment, 2024)

TaSRT2 recognizes a viral protein to activate host immunity by increasing histone acetylation - Kaili Zhong; Yaoyao Jiang; Haichao Hu; Bowen Yuan; Mila Wu; Aizhu Tu; Gecheng Xu; Linna Cai; Tingting Liu; Shiqi Gao; Linzhi Li; Qiansheng Liao; et al. (Science Bulletin, 2024)

Analysis the sewage sludge recycling strategy based on real-time pyrolysis performance and pyrochar characteristics - Jingjing Chen; Yuping Zheng; Mengyan Lv; Tingting Zhao; Qingqi Lin; Zhuobiao Ni; Zuotai Zhang; Rongliang Qiu (Journal of Cleaner Production, 2024)

Identification of effective components in Flos Chrysanthemi Indici for alleviating gouty inflammation through integrated absorption and metabolism studies - Yuting Huang; Tingting Xu; Yanan Yuan; Lin Xiang; Ting Wu; Siyi Pan; Xiaoyun Xu (Food Bioscience, 2024)

Bimetallic loaded ZIF-8 with peroxidase-like and photothermal activities for sensitive detection and efficient elimination of Listeria monocytogenes - Tingting Su; Yuting Chang; Minghui Lu; Xianfeng Lin; Zhiyuan Ning; Shijia Wu; Zhouping Wang; Nuo Duan (Chemical Engineering Journal, 2024)

In-situ complexation of Cu(II) with polyethyleneimine (PEI) triggers the enhanced formation of halonitromethanes, dichloroacetonitrile, and dichloroacetamide during UV/chlorine disinfection: Cu(I) contribution and Cl· sustainable production - Tingting Huang; Shui Wang; Lin Deng; Qian Tang; Chaoqun Tan; Zhihua Yin; Daoxu Zhong; Lianghua Lu; Yasong Feng (Chemical Engineering Journal, 2024)

Gut microbiota dynamics in KK-Ay mice: restoration following antibiotic treatment - Jinni Hong; Tingting Fu; Weizhen Liu; Miao Yu; Yanshan Lin; Cunyun Min; Datao Lin (Folia Microbiologica, 2024)

Transcriptomics to evaluate the influence mechanisms of ethanol on the ester production of Wickerhamomyces anomalus with the induction of lactic acid - Wenqin Cai; Yin Wan; Yanru Chen; Haowei Fan; Mengxiang Li; Shengwen Wu; Pei Lin; Tingting Zeng; Huibo Luo; Dan Huang; Guiming Fu (Food Microbiology, 2024)

Macrophage-Targeted multifunctional nanoparticles for detection and treatment of intraplaque hemorrhage - Haiyang Wang; Min Zheng; Yushi Chen; Long Cheng; Xiaotong Qi; Huilin Yu; Jianming Sun; Junjie Liu; Ruoyao Wang; Yaqin Hu; Tao Lin; Ying Zhang; et al. (Chemical Engineering Journal, 2024)

Enrichment pattern of tungsten in sediments under methane seepage environments: Applicability as a proxy for tracing and reconstructing (paleo-)methane seepage - Xiaoming Miao; Davide Oppo; Jiangong Wei; Zhiyong Lin; Xiting Liu; Tingting Wu; Xi Yu; Kaikai Wu; Jingrui Li (Chemical Geology, 2024)

Bavachinin, a main compound of Psoraleae Fructus, facilitates GSDMD-mediated pyroptosis and causes hepatotoxicity in mice - Wei Shi; Yuan Gao; Huijie Yang; Hui Li; Tingting Liu; Jia Zhao; Ziying Wei; Li lin; Yujiao Huang; Yuming Guo; Anlong Xu; Zhaofang Bai; et al. (Chemico-Biological Interactions, 2024)

Identifying the physiological and behavioral responsiveness to characterize the stress coping style in the large yellow croaker (Larimichthys crocea) - Siping Li; Tingting Lin; Xin Liu; Xiaoshan Wang; Shengyu Liu; Dong Zhang (Aquaculture, 2024)

Effects of Fe(III) on the formation and toxicity alteration of halonitromethanes, dichloroacetonitrile, and dichloroacetamide from polyethyleneimine during UV/chlorine disinfection - Tingting Huang; Lin Deng; Shui Wang; Chaoqun Tan; Jun Hu; Bingqing Zhu; Mengya Li; Lianghua Lu; Zhihua Yin; Bowen Fu (Water Research, 2024)

Preharvest GA3 treatment at optimized time points enhanced the storability of ‘Shixia’ longan fruit - Tao Luo; Libing Long; Tingting Lai; Xiaolan Lin; Chenning Ning; Ziying Lai; Xinxin Du; Liang Shuai; Dongmei Han; Zhenxian Wu (Postharvest Biology and Technology, 2024)

Resveratrol ameliorates cyprodinil-induced zebrafish cardiac developmental defects as an aryl hydrocarbon receptor antagonist - Ruyu Zhan; Fushan Zhou; Chaoyang Liu; Chuanchang Chen; Mingmei Li; Dongqin Huang; Naying Zheng; Tingting Lin; Zhenghong Zuo; Chengyong He; Xintan Chen (Environmental Science and Pollution Research, 2024)

Monitoring system for peanut leaf disease based on a lightweight deep learning model - Yongda Lin; Linhui Wang; Tingting Chen; Yajia Liu; Lei Zhang (Computers and Electronics in Agriculture, 2024)

Above- and belowground phenology responses of subtropical Chinese fir (Cunninghamia lanceolata) to soil warming, precipitation exclusion and their interaction - Zekun Qu; Chengfang Lin; Haiying Zhao; Tingting Chen; Xiaodong Yao; Xiaohong Wang; Yusheng Yang; Guangshui Chen (Science of The Total Environment, 2024)

BaO-modified finger-like nickel-based anode for enhanced performance and durability of direct carbon solid oxide fuel cells - Lin Li; Yujiao Xie; Tingting Han; Jinjin Zhang; Fangyong Yu; Gen Li; Jaka Sunarso; Naitao Yang; Yongdan Li (Fuel, 2024)

Effect of microwave alone and microwave-assisted modification on the physicochemical properties of starch and its application in food - Mingxia Yi; Xuchong Tang; Shaoxiong Liang; Ren He; Tingting Huang; Qing Lin; Rongjun Zhang (Food Chemistry, 2024)

Rheological and microstructural characterization of lotus seed milks and their glucono-δ-lactone induced acid-set milk gels: 2. effect of oil addition - Zhao Li; Tingting Li; Xiaoqian Lin; Meng Zhao; Yacine Hemar (Food Hydrocolloids, 2024)

Surface topography and chemistry of food contact substances, and microbial nutrition affect pathogen persistence and symbiosis in cocktail Listeria monocytogenes biofilms - Tingting Gu; Yaguang Luo; Zhen Jia; Apisak Meesrison; Sophia Lin; Isabella J. Ventresca; Sarah J. Brooks; Arnav Sharma; Sitara Sriram; Manyun Yang; Arne J. Pearlstein; Patricia D. Millner; et al. (Food Control, 2024)

Identification of a novel glycoside hydrolase family 8 xylanase from Deinococcus geothermalis and its application at low temperatures - Tingting Wang; Min Lin; Yongliang Yan; Shijie Jiang; Qilin Dai; Zhengfu Zhou; Jin Wang (Archives of Microbiology, 2024)

Brooding fathers actively consume viable embryos to take up nutrients in a monogamous syngnathid fish - Tingting Lin; Xin Liu; Siping Li; Dong Zhang; Fengyuan Shen (Frontiers in Marine Science, 2024)
Syngnathid fishes often experience a reduction in brood size and an increase in immunity during pregnancy. Researchers have studied the polygamous broad-nosed pipefish ( Syngnathus typhle ) and revealed that some eggs from low-quality females in the male’s brood pouch serve as nurse eggs that are absorbed by the father. It is unclear whether nurse eggs also exist in other syngnathid fishes, especially in monogamous syngnathid fishes. In monogamous syngnathid fishes, the male pouch only carries eggs from a single female. Thus, the question remains: do some eggs of monogamous syngnathid fishes also serve as nurse eggs? And if so, are these nurse eggs impaired eggs, or are they viable eggs that are consumed by the brooding father? In the present study, we used the monogamous lined seahorse ( Hippocampus erectus ) and asked whether nurse eggs exist in this species. We also explored whether nurse eggs potentially originate from viable versus inviable eggs. Using isotope labeling, we found that nutrients from embryos could be transferred to brooding fathers. Furthermore, we also found that brooding fathers with limited food had a higher isotope content and a smaller brood size compared to individuals with sufficient food. These results have demonstrated that nurse eggs exist in the lined seahorse, and also suggested that the brooding fathers actively consume viable embryos to absorb nutrients in response to low food availability. These findings help us better understand parent–embryo conflict, filial cannibalism, and male-only care in teleost fishes.

Promoting the denitrification process by heavy metals in Liaohe Estuary sediment - Ming Hongxia; Zan Shuaijun; Liu Jiwen; Su Jie; Ren Kaijia; Lin Jiannan; Chen Quanrui; Shi Yinyin; Shi Tingting; Fan Jingfeng (Marine Pollution Bulletin, 2024)

Therapy of liver fibrosis: From conventional approaches to nanomaterials delivery systems - Lin Chen; Yu Duan; Tingting Jiang; Chun Mao; Xinhua Zhu; Mimi Wan (Science Bulletin, 2024)

The improvement effects of Lentinus edodes powder marination on sous vide cooked chicken patties: Physicochemical attributes, oxidative properties and flavor characteristics - Menglong Sheng; Songyi Lin; Tingting Ma; Lei Qin; Yixin Chang; Dong Chen (Food Chemistry, 2024)

Enhanced lanthanum and cerium removal of self-powered electro-membrane bioreactor (SPEMBR) using high-active bi-functional M-N-CNTs@Fe/Mo electrode - Hui Lu; Hongbo Wang; Changfei Gao; Lifen Liu; Tingting Yu; Yihua Li; Shaoying Lin (Chemical Engineering Journal, 2024)

Analysis of PIN Gene Family in Cymbidium ensifolium Revealed its Potential Function in Petal Development - Jiayi Chen; Peng Li; Longwei Xiong; Jinlan Lin; Liting Guo; Lu Yan; Tingting Huang; Ye Ai (Tropical Plant Biology, 2024)

Sugarcane ScOPR1 gene enhances plant disease resistance through the modulation of hormonal signaling pathways - Wenhui Zou; Tingting Sun; Yao Chen; Dongjiao Wang; Chuihuai You; Shoujian Zang; Peixia Lin; Qibin Wu; Yachun Su; Youxiong Que (Plant Cell Reports, 2024)

Synergistically Augmenting Cancer Immunotherapy by Physical Manipulation of Pyroptosis Induction - Chenyang Zhao; Tingting Zheng; Run Wang; Xiaona Lin; Zhengming Hu; Zhuofei Zhao; Zhifei Dai; Desheng Sun (Phenomics, 2024)
Pyroptosis is a newly recognized type of programmed cell death mediated by the gasdermin family and caspase. It is characterized by the formation of inflammasomes and the following inflammatory responses. Recent studies have elucidated the value of pyroptosis induction in cancer treatment. The inflammatory cytokines produced during pyroptosis can trigger immune responses to suppress malignancy. Physical approaches for cancer treatment, including radiotherapy, light-based techniques (photodynamic and photothermal therapy), ultrasound-based techniques (sonodynamic therapy and focused ultrasound), and electricity-based techniques (irreversible electroporation and radiofrequency ablation), are effective in clinical application. Recent studies have reported that pyroptosis is involved in the treatment process of physical approaches. Manipulating pyroptosis using physical approaches can be utilized in combating cancer, according to recent studies. Pyroptosis-triggered immunotherapy can be combined with the original anti-tumor methods to achieve a synergistic therapy and improve the therapeutic effect. Studies have also revealed that enhancing pyroptosis may increase the sensitivity of cancer cells to some physical approaches. Herein, we present a comprehensive review of the literature focusing on the associations between pyroptosis and various physical approaches for cancer and its underlying mechanisms. We also discussed the role of pyroptosis-triggered immunotherapy in the treatment process of physical manipulation.

Identification of Key Factors in Cartilage Tissue During the Progression of Osteoarthritis Using a Non-targeted Metabolomics Strategy - Shiyu Sun; Minghui Chen; Tingting Zhang; Yanyan Wang; Weijun Shen; Tao Zhang; Jian Liu; Haidan Lan; Jianyuan Zhao; Fuqing Lin; Xuan Zhao (Phenomics, 2024)
This research was to reveal the key factors in the progression of osteoarthritis (OA) using non-targeted metabolomics and to find targeted therapies for patients with OA. Twenty-two patients with knee OA scheduled for total knee arthroplasty were divided into two groups: Kellgren–Lawrence (KL) grade 3 ( n = 16) and grade 4 ( n = 6), according to plain X-rays of the knee. After the operation, the cartilages of femur samples were analyzed using non-targeted metabolomics. When compared with grade 3 patients, the levels of choline, 2-propylpiperidine, rhamnose, and monomethyl glutaric acid were higher; while 1-methylhistamine, sphingomyelin (SM) (d18:1/14:0), zeranol, 3- (4-hydroxyphenyl)-1-propanol, 5-aminopentanamide, dihydrouracil, 2-hydroxypyridine, and 3-amino-2-piperidone were lower in grade 4 patients. Furthermore, some metabolic pathways were found to be significantly different in two groups such as the pantothenate and coenzyme A (CoA) biosynthesis pathway, the glycerophospholipid metabolism pathway, histidine metabolism pathway, lysine degradation pathway, glycine, serine and threonine metabolism pathway, fructose and mannose metabolism pathway, the pyrimidine metabolism pathway, and beta-alanine metabolism pathway. This work used non-targeted metabolomics and screened out differential metabolites and metabolic pathways, providing a reliable theoretical basis for further study of specific markers and their specific pathways in the progression of OA.

Zinc-a2-Glycoprotein Acts as a Component of PNN to Protect Hippocampal Neurons from Apoptosis - Kewei Chang; Liyan Lin; Tingting Cui; Hao Zhao; Jiaxin Li; Chang Liu; Dan Gao; Shemin Lu (Molecular Neurobiology, 2024)

IFITM1 and IFITM2 inhibit the replication of senecavirus A by positive feedback with RIG-I signaling pathway - Huizi Li; Ming Chen; Tingting Zheng; Xiaoling Lei; Cunhao Lin; Shuo Li; Jiacong Mo; Zhangyong Ning (Veterinary Microbiology, 2024)

Formation and toxicity alteration of halonitromethanes from Chlorella vulgaris during UV/chloramination process involving bromide ion - Qian Tang; Lin Deng; Yuyang Mao; Shuang Fu; Wei Luo; Tingting Huang; Jun Hu; Rajendra Prasad Singh (Journal of Environmental Management, 2024)

The Mh-miR393a-TIR1 module regulates Alternaria alternata resistance of Malus hupehensis mainly by modulating the auxin signaling - Xinyi Yu; Kaixu Hu; Xiaoyue Geng; Lifang Cao; Tingting Zhou; Xinxin Lin; Hongcheng Liu; Jingrui Chen; Changguo Luo; Shenchun Qu (Plant Science, 2024)

Biodegradation of polystyrene by bacteria isolated from the yellow mealworm (Tenebrio molitor) gut - Wen Lin; Yu Yao; Tingting Su; Zhanyong Wang (Journal of Environmental Chemical Engineering, 2024)

Letrozole induced a polycystic ovary syndrome model in zebrafish by interfering with the hypothalamic-pituitary-gonadal axis - Fucong Zhang; Chen Tang; Jingyi Wang; Tingting Lin; Wei Ge; Chengyong He; Chunyan Yang; Zhenghong Zuo (Environmental Pollution, 2024)

Well plate-based LF-NMR/colorimetric dual-mode homogeneous immunosensor for Vibrio parahaemolyticus detection - Dongyu Zhang; Le Chen; Han Lin; Tingting Hao; Yangbo Wu; Jianjun Xie; Xizhi Shi; Xiaohua Jiang; Zhiyong Guo (Food Chemistry, 2024)

Direct generation of high-valent iron-oxo species to eliminate oxytetracycline at circumneutral pH via paper mill sludge ash activating peroxymonosulfate - Tingting Lin; Huajing Zhou; Lingxiang Zhao; Sheng Liang; Yongming Luo; Liang He; Shaoyun Shan; Tianding Hu; Zilian Liu; Wentao Du (Chemical Engineering Journal, 2024)

K-promoted Ru-based heterogeneous catalysts for ethylene hydroformylation - Dinghao Cui; Tingting Qin; Tiejun Lin; Jingrui Ti; Yunlei An; Liangshu Zhong (Chemical Engineering Journal, 2024)

Long-term stable and efficient degradation of ornidazole with minimized by-product formation by a biological sulfidogenic process based on elemental sulfur - Jiajia Zeng; Shuqun Xu; Keyue Lin; Si Yao; Bin Yang; Zhanhui Peng; Tianwei Hao; Xiaoyu Yu; Tingting Zhu; Feng Jiang; Jianliang Sun (Water Research, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

A tale of two vein types: Bed-parallel fibrous versus blocky filled fractures in organic-rich shales and their overpressured hydrocarbon fluids - Miao Wang; Feng Liang; Tong Lin; Yelei Wang; Hui Zhang; Qian Huang; Yifan Song; Tingting Liu; Yanwei Feng; Rui Ni; Xiaoying Guo; Tengfei Zhou; et al. (Marine and Petroleum Geology, 2024)

Cardiac energy metabolism disorder mediated by energy substrate imbalance and mitochondrial damage upon tebuconazole exposure - Tingting Ku; Jindong Hu; Mengmeng Zhou; Yuanyuan Xie; Yutong Liu; Xin Tan; Lin Guo; Guangke Li; Nan Sang (Journal of Environmental Sciences, 2024)

In situ biomass burning enhanced the contribution of biogenic sources to sulfate aerosol in subtropical cities - Tingting Li; Jun Li; Luhua Xie; Boji Lin; Hongxing Jiang; Rong Sun; Xiao Wang; Ben Liu; Chongguo Tian; Qilu Li; Wanglu Jia; Gan Zhang; et al. (Science of The Total Environment, 2024)

Numerical and experimental study of oil boom motion response and oil-stopping effect under wave-current action - Tingting Hou; Hongyuan Sun; Bo Jiao; Guoxing Wang; Haihua Lin; Hao Liu; Bo Gao (Ocean Engineering, 2024)

Discrimination of toxigenic and non-toxigenic Aspergillus flavus in wheat based on nanocomposite colorimetric sensor array - Zeyu Chen; Hao Lin; Fuyun Wang; Selorm Yao-Say Solomon Adade; Tingting Peng; Quansheng Chen (Food Chemistry, 2024)

A study on identifying synergistic prevention and control regions for PM2.5 and O3 and exploring their spatiotemporal dynamic in China - Haojie Wu; Bin Guo; Tengyue Guo; Lin Pei; Peiqing Jing; Yan Wang; Xuying Ma; Haorui Bai; Zheng Wang; Tingting Xie; Miaoyi Chen (Environmental Pollution, 2024)

Enhanced remediation of Cr(VI)-contaminated soil by modified zero-valent iron with oxalic acid on biochar - Lihong Xie; Qingjun Chen; Yiyang Liu; Qiyan Ma; Jinlan Zhang; Chenliu Tang; Guilan Duan; Aijun Lin; Tingting Zhang; Shangyi Li (Science of The Total Environment, 2023)

Comparison of microalgae cultivation modes for advanced wastewater purification and pollutant-resource conversion: A pilot study - Lin-Lan Zhuang; Pengfei Yang; Shuang Liang; Tong Yu; Chao Liu; Tingting Zhao; Guoliang Tan; Yueying Niu; Jian Zhang (Journal of Water Process Engineering, 2023)

Multi-objective optimization of gas-steam-power system for an integrated iron and steel mill considering carbon emission reduction and cost - Tingting Xu; Zhaoyi Huo; Tong Wang; Jiawei Lv; Yixuan Han; Lin Mu (Journal of Cleaner Production, 2023)

Remediation of Cr(VI)-contaminated soil by ball milling modified zero-valent iron biochar composites: Insights into long-term stability and microbial community - Pengfei Guo; Jinlan Zhang; Yi Zhou; Chenliu Tang; Xiaohui Wang; Xiaoping Gao; Guilan Duan; Aijun Lin; Tingting Zhang; Shangyi Li (Journal of Environmental Chemical Engineering, 2023)

Green and ultrastrong polyphenol lignin-based vitrimer adhesive with photothermal conversion property, wide temperature adaptability, and solvent resistance - Yanfan Yang; Hao Zhou; Xiaoqi Chen; Tingting Liu; Yong Zheng; Lin Dai; Chuanling Si (Chemical Engineering Journal, 2023)

Influencing Factors and New Reference Intervals of Adult Thyroid Volume in Iodine-Sufficient Areas of China - Zheyu Lin; Cihang Lu; Di Teng; Ying Sun; Tingting Liu; Yongze Li; Zhongyan Shan; Weiping Teng (Biological Trace Element Research, 2023)
The diagnosis of goiter is based on the thyroid volume measured by ultrasound in which iodine plays an important role. The purpose of this study was to evaluate the factors that affect thyroid volume and update the reference range of thyroid volume to provide a new basis for the diagnosis and treatment of goiter. A study population from mainland China was evaluated in the Thyroid disorders, Iodine status and Diabetes Epidemiological (TIDE) study. Thyroid size was measured by ultrasound, and thyroid volume was calculated. A quantile regression model was used to analyze the influence of related factors on the thyroid volume at each percentile. The median urinary iodine concentration (UIC) was 185.54 μg/l. The quantile regression model suggested that body surface area (BSA) and thyroid-stimulating hormone (TSH) were positive and negative factors for thyroid volume, respectively ( p < 0.01). Excess iodine reduces the median and lower limits of thyroid volume. In iodine-sufficient areas, smoking is no longer a risk factor. The reference value range of thyroid volume stratified by sex was 3.92–19.06 ml for males and 3.1–16.17 ml for females. The maximum reference ranges for stratification by sex and BSA were 4.25–20.98 ml for men and 3.44–18.31 ml for women. The iodine nutrition level of the population in mainland China is sufficient. Iodine has the potential to alter the effect of certain factors on thyroid volume and effect is not regional. The new reference interval of adult thyroid volume based on sex and BSA has been updated, which can be used as a reliable reference for updating the diagnostic criteria of endemic goiter.

An N-N linked dimeric indole alkaloid from the marine sponge-associated rare actinomycetes Kocuria sp. S42 - Jingwei Jia; Xiaozheng Wang; Jin Sang; Zhiyong Li; Shuangjun Lin; Zixin Deng; Tingting Huang (Natural Product Research, 2023)

Performance of Doppler shift compensation varies with environmental temperature and humidity in bats - Jianan Ding; Fujie Han; Kangkang Zhang; Aiqing Lin; Tingting Jiang; Jiang Feng; Ying Liu (Animal Behaviour, 2023)

Sulfurization alters phenol-formaldehyde resin microplastics redox property and their efficiency in mediating arsenite oxidation - Lin Chen; Tingting Fan; Min Yang; Dunfeng Si; Haotian Wu; Song Wu; Jian Xu; Dongmei Zhou (Science of The Total Environment, 2023)

Differential treatment for time and frequency dimensions in mel-spectrograms: An efficient 3D Spectrogram network for underwater acoustic target classification - Ning Tang; Fei Zhou; Yan Wang; Hao Zhang; Tingting Lyu; Zhen Wang; Lin Chang (Ocean Engineering, 2023)

Identifying the role of array electrodes in improving the compost quality of food waste during electric field-assisted aerobic composting - Huan Mi; Chang Shen; Tingting Ding; Xincheng Zheng; Jiahuan Tang; Hao Lin; Shungui Zhou (Bioresource Technology, 2023)

Correction to: Antioxidative effects of polypyrimidine tract-binding protein-associated splicing factor against pathological retinal angiogenesis through promotion of mitochondrial function - Lijie Dong; Tingting Lin; Wenbo Li; Yaru Hong; Xinjun Ren; YiFeng Ke; Xiaomin Zhang; Xiaorong Li (Journal of Molecular Medicine, 2023)

Effects of phosphorus stress on the growth and secondary metabolism of Artemisia argyi - Zixin Wang; Lin Ma; Changjie Chen; Lujuan Guo; Lanping Guo; Tingting Zhao; Dahui Liu (Journal of Plant Research, 2023)

Contrasting laboratory and field outcomes of bat–moth interactions - Aiqing Lin; Jiqian Li; Yinli Hu; Maojun Zhong; Minglun Yu; Nina Ma; Tingting Wei; Jinhong Luo; Jiang Feng (Molecular Ecology, 2023)
Predator–prey interactions are important but difficult to study in the field. Therefore, laboratory studies are often used to examine the outcomes of predator–prey interactions. Previous laboratory studies have shown that moth hearing and ultrasound production can help prey avoid being eaten by bats. We report here that laboratory behavioural outcomes may not accurately reflect the outcomes of field bat–moth interactions. We tested the success rates of two bat species capturing moths with distinct anti‐bat tactics using behavioural experiments. We compared the results with the dietary composition of field bats using next‐generation DNA sequencing. Rhinolophus episcopus and Rhinolophus osgoodi had a lower rate of capture success when hunting for moths that produce anti‐bat clicks than for silent eared moths and earless moths. Unexpectedly, the success rates of the bats capturing silent eared moths and earless moths did not differ significantly from each other. However, the field bats had a higher proportion of silent eared moths than that of earless moths and that of clicking moths in their diets. The difference between the proportions of silent eared moths and earless moths in the bat diets can be explained by the difference between their abundance in bat foraging habitats. These findings suggest that moth defensive tactics, bat countertactics and moth availability collectively shape the diets of insectivorous bats. This study illustrates the importance of using a combination of behavioural experiments and molecular genetic techniques to reveal the complex interactions between predators and prey in nature.

Diffusion kurtosis imaging tractography reveals disrupted white matter structural networks in children with obstructive sleep apnea syndrome - Yanhua Li; Hongwei Wen; Wenfeng Li; Yun Peng; Hongbin Li; Jun Tai; Tingting Ji; Lin Mei; Yue Liu (Brain Imaging and Behavior, 2023)

Experimental study on Diels-Alder addition of conjugated dienes directly from cracking C5 fraction by continuous micro-channel reactors - Zehao Jing; Tingting Ge; Hui Guo; Yuchao Li; Zhou Li; Cuncun Zuo; Ming Wang; Haofei Huang; Lin Guo; Guangjun Cui (Fuel, 2023)

Carboxyl-containing components delineation via feature-based molecular networking: A key to processing conditions of fermented soybean - Yuye Gao; Yu Fu; Na Li; Yuetong Jiang; Xiaojing Liu; Congcong Gao; Lishuang Wang; Jian-Lin Wu; Tingting Zhou (Food Chemistry, 2023)

Low-temperature thermally enhanced bioremediation of polycyclic aromatic hydrocarbon-contaminated soil: Effects on fate, toxicity and bacterial communities - Jun Zeng; Ruini Wu; Tingting Peng; Qigang Li; Qing Wang; Yucheng Wu; Xin Song; Xiangui Lin (Environmental Pollution, 2023)

Impact of COVID-19 pandemic on profiles of antibiotic-resistant genes and bacteria in hospital wastewater - Liang Zhao; Ziquan Lv; Liangqiang Lin; Xiaowei Li; Jian Xu; Suli Huang; Yuhua Chen; Yulin Fu; Changfeng Peng; Tingting Cao; Yuebin Ke; Xi Xia (Environmental Pollution, 2023)

Response Surface Methodology and Artificial Neural Network Modeling for the Removal of Volatile Organic Compounds in Biotrickling Filters - Tianqiu Hong; Lin Wei; Kangping Cui; Yugang Dong; Lei Luo; Tingting Zhang; Ruolan Li; Ziyue Li; Yiming Tang (Water, Air, & Soil Pollution, 2023)

Astringin protects LPS-induced toxicity by suppressing oxidative stress and inflammation via suppression of PI3K/AKT/NF-κB pathway for pediatric acute lung injury - Ling Wang; Shanshan Jiang; Xiaoxiao Li; Tingting Lin; Tao Qin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

PLK3 promotes the proneural–mesenchymal transition in glioblastoma via transcriptional regulation of C5AR1 - Shuo Yu; Lin Lv; Yang Li; Qian Ning; Tingting Liu; Tinghua Hu (Molecular Biology Reports, 2023)

Critical Roles of Protein Arginine Methylation in the Central Nervous System - Kewei Chang; Dan Gao; Jidong Yan; Liyan Lin; Tingting Cui; Shemin Lu (Molecular Neurobiology, 2023)

Co-exposure to iron, copper, zinc, selenium and titanium is associated with the prevention of gastric precancerous lesions - Tingting Wang; Fang Xu; Xiao Lin; Yaning Lv; Xiaohui Zhang; Wenli Cheng; Li Wang; Min Wang; Meng Zhang; Tao Xia; Shiqing Qian; Min Tang; et al. (BioMetals, 2023)

New mechanisms of biochar-assisted vermicomposting by recognizing different active di-(2-ethylhexyl) phthalate (DEHP) degraders across pedosphere, charosphere and intestinal sphere - Shuwen Luo; Zhen Zhen; Tingting Teng; Weilong Wu; Guiqiong Yang; Changhong Yang; Huijun Li; Fengcheng Huang; Ting Wei; Zhong Lin; Dayi Zhang (Journal of Hazardous Materials, 2023)

Clinical poisoning events involving yunaconitine may be highly correlated with metabolism-based interactions: A critical role of CYP3A4 - Xiaocui Li; Yu Fu; Huawei Qiu; Xueyu Xu; Tingting Lin; Weiqing Hou; Weiying Chen; Rong Zhang; Zhongqiu Liu; Lijun Zhu (Food and Chemical Toxicology, 2023)

Nitrogen-doped carbon coated zinc as powder-based anode with PVA-gel electrolyte enhancing cycling performance for zinc-ion batteries - Yunhui Lin; Ming Zhang; Youzuo Hu; Shu Zhang; Ziqiang Xu; Tingting Feng; Haiping Zhou; Mengqiang Wu (Chemical Engineering Journal, 2023)

Complete conversion of xylose-extracted corncob residues to bioplastic in a green and low carbon footprint way - Hao Zhou; Yingrong Mao; Yong Zheng; Tingting Liu; Yanfan Yang; Chuanling Si; Lei Wang; Lin Dai (Chemical Engineering Journal, 2023)

Retraction Note: Antioxidative effects of polypyrimidine tract-binding protein-associated splicing factor against pathological retinal angiogenesis through promotion of mitochondrial function - Lijie Dong; Tingting Lin; Wenbo Li; Yaru Hong; Xinjun Ren; YiFeng Ke; Xiaomin Zhang; Xiaorong Li (Journal of Molecular Medicine, 2023)

The validity and international comparability of China’s floating population concepts and data - Yu Zhu; Liyue Lin; Tingting Li; Yajing Dong (Journal of Geographical Sciences, 2023)

A review on processing methods and functions of wheat germ-derived bioactive peptides - Zebin Weng; Yuanrong Chen; Tingting Liang; Yajuan Lin; Hui Cao; Haizhao Song; Ling Xiong; Fang Wang; Xinchun Shen; Jianbo Xiao (Critical Reviews in Food Science and Nutrition, 2023)

Influence of circulation types on temporal and spatial variations of ozone in Beijing - Xiaowan Zhu; Jin Wu; Guiqian Tang; Lin Qiao; Tingting Han; Xiaomei Yin; Xiangxue Liu; Ziming Li; Yajun Xiong; Di He; Zhiqiang Ma (Journal of Environmental Sciences, 2023)

Boosting the tumor photothermal therapy with hollow CoSnSx-based injectable hydrogel via the sonodynamic and dual-gas therapy - Lu Jia; Yuzhu Wang; Tingting Hu; Chunyu Yang; Huiming Lin; Feng Zhang; Fengyu Qu; Liru Cui; Wei Guo (Chemical Engineering Journal, 2023)

Isolation of rhizobacteria from the Cenchrus fungigraminus rhizosphere and characterization of their nitrogen-fixing performance and potential role in plant growth promotion - Jing Li; Bingxin Zhou; Tingting Li; Hui Lin; Zhanxi Lin; Guodong Lu; Yanling Liu; Biaosheng Lin; Dongmei Lin (Plant and Soil, 2023)

Impact of Primary Container Closure System on PS80 Oxidation and the Mechanistic Understanding - Ryan Mould; Peter William Sargent; Yining Huang; Allison L. Fields; Lin Zhang; Fabian Castro Herbert; Stephanie Lynn Stewart; Tingting Wang (Pharmaceutical Research, 2023)

Applying machine learning to fine classify construction and demolition waste based on deep residual network and knowledge transfer - Kunsen Lin; Youcai Zhao; Tingting Zhou; Xiaofeng Gao; Chunbo Zhang; Beijia Huang; Qinyan Shi (Environment, Development and Sustainability, 2023)

Dynamic soil arching in piled embankment under train load of high-speed railways - Tingting Niu; Yule Yang; Qianli Ma; Jiuqun Zou; Bin Lin (Earthquake Engineering and Engineering Vibration, 2023)

Multiscale Feature Fusion for Hyperspectral Marine Oil Spill Image Segmentation - Guorong Chen; Jiaming Huang; Tingting Wen; Chongling Du; Yuting Lin; Yanbing Xiao (Journal of Marine Science and Engineering, 2023)
Oil spills have always been a threat to the marine ecological environment; thus, it is important to identify and divide oil spill areas on the ocean surface into segments after an oil spill accident occurs to protect the marine ecological environment. However, oil spill area segmentation using ordinary optical images is greatly interfered with by the absorption of light by the deep sea and the distribution of algal organisms on the ocean surface, and it is difficult to improve segmentation accuracy. To address the above problems, a hyperspectral ocean oil spill image segmentation model with multiscale feature fusion (MFFHOSS-Net) is proposed. Specifically, the oil spill segmentation dataset was created using hyperspectral image data from NASA for the Gulf of Mexico oil spill, small-size images after the waveband filtering of the hyperspectral images were generated and the oil spill images were annotated. The model makes full use of having different layers with different characteristics by fusing feature maps of different scales. In addition, an attention mechanism was used to effectively fuse these features to improve the oil spill region segmentation accuracy. A case study, ablation experiments and model evaluation were also carried out in this work. Compared with other models, our proposed method achieved good results according to various evaluation metrics.

The interspecific competition of tree plants in the presence of AM fungi and litter facilitates root morphological development and nutrition when compared with intraspecific competition - Yun Guo; Kaiping Shen; Tingting Xia; Yuejun He; Wenda Ren; Pan Wu; Yan Lin; Bangli Wu; Xu Han; Lu Gao; Jinting Li; Xiaorun Hu; et al. (Environmental Science and Pollution Research, 2023)

Genome-wide methylome and transcriptome dynamics provide insights into epigenetic regulation of kidney functioning of large yellow croaker (Larimichthys crocea) during low-salinity adaption - Jian Yang; Minhai Liu; Tingting Zhou; Qi Li; Zhihua Lin (Aquaculture, 2023)

Arl13b promotes the proliferation, migration, osteogenesis, and mechanosensation of osteoblasts - Tingting Lin; Yao Sun (Tissue and Cell, 2023)

DNA barcoding identification of IUCN Red listed threatened species in the genus Aquilaria (Thymelaeaceae) using machine learning approaches - Yuexia Lin; Tingting Feng; Jiangpeng Dai; Qiaozhen Liu; Yiming Cai; Jiarong Kuang; Zhaoyu Wang; Xiaoxia Gao; Shaofeng Liu; Shuang Zhu (Phytochemistry Letters, 2023)

Revealing and quantifying the effect of cattiite coprecipitation on the purity of K-struvite in aqueous solution - Lin Wei; Tingting Zhang; Tianqiu Hong; Yugang Dong; Dongdong Ji; Lei Luo; Ruolan Li; Ziyue Li; Yiming Tang (Journal of Environmental Chemical Engineering, 2023)

Enhancement of the release of phenolic compounds from white and black Qingke bran by autoclaving and fermentation treatments - Caian He; Xiaojiao Liu; Haiyan Zhang; Tingting Mu; Yuhong Zhang; Xuechun Ren; Lin Han; Min Wang (Food Bioscience, 2023)

Experimental and numerical study of micro-tubular direct carbon solid oxide fuel cell fueled by the oilseed rape straw-derived biochar - Tingting Han; Yujiao Xie; Lin Li; Ke Miao; Yu Mei; Jian Song; Jinjin Zhang; Xiuxia Meng; Ngie Hing Wong; Jaka Sunarso; Fangyong Yu; Naitao Yang (Chemical Engineering Journal, 2023)

An injectable antibacterial hydrogel to regulate ocular immune for endophthalmitis treatment - Zunzhen Ming; Lin Han; Huanhuan Zhu; Meiyu Bao; Qiangyuan Fan; Shaobo Xue; Kesheng Wang; Yue Zhang; Meiling Lu; Chongshun Xu; Qi Wu; Tingting Li; et al. (Chemical Engineering Journal, 2023)

Legacy effect of plant chemical defence substances on litter decomposition - Yunchao Luo; Lin Wang; Tingting Cao; Weihua He; Shangxian Lu; Fei Li; Zhenwei Zhang; Tong Chang; Xingjun Tian (Plant and Soil, 2023)

DNA barcoding authentication of Uncaria species using machine learning approaches - Qiaozhen Liu; Yiming Cai; Jiangpeng Dai; Jiarong Kuang; Tingting Feng; Xiaoxia Gao; Yuexia Lin; Shuang Zhu (Acta Physiologiae Plantarum, 2023)

An effective biological treatment method for marine aquaculture wastewater: Combined treatment of immobilized degradation bacteria modified by chitosan-based aerogel and macroalgae (Caulerpa lentillifera) - Tingting Ye; Min Li; Yuanbin Lin; Zengjian Su (Aquaculture, 2023)

Measuring segregation in fluidized bed with magnetizable and nonmagnetizable particles based on magnetic permeability - Quanhong Zhu; Qiang Zhang; Peiyi Yang; Hengjun Gai; Mengqi Lin; Hongbing Song; Meng Xiao; Tingting Huang (Fuel, 2023)

Lithiophilic interface dynamic engineering to inhibit Li dendrite growth for intrinsically safe Li-metal batteries - Tingting Jiang; Lingling Sun; Yao Zhang; Xiaomin Zhang; Huijuan Lin; Kun Rui; Jixin Zhu (Chemical Engineering Journal, 2023)

Variable p53/Nrf2 crosstalk contributes to triptolide-induced hepatotoxic process - Zhenyan Hou; Miao Yan; Huixiang Li; Weida Wang; Shen You; Mingjin Wang; Tingting Du; Hui Gong; Wenqun Li; Lin Guo; Shanshan Wei; Bikui Zhang; et al. (Toxicology Letters, 2023)

New methods based on a genetic algorithm back propagation (GABP) neural network and general regression neural network (GRNN) for predicting the occurrence of trihalomethanes in tap water - Kangle Liu; Tao Lin; Tingting Zhong; Xinran Ge; Fuchun Jiang; Xue Zhang (Science of The Total Environment, 2023)

Highly sensitive detection of lead ions and cadmium ions based on ZIF-8-NH2 enhanced by carbon nanotubes and bismuth film - Xingguang Chen; Tingting Xie; Chaoqun Lu; Jiyang Chu; Wenzhe Li; Rui Lin; Dianhui Wu; Qianhui Gu (Journal of Environmental Chemical Engineering, 2023)

Dual-dense gas-solid circulating fluidized bed reactor - Hengjun Gai; Peiyi Yang; Qiang Zhang; Mengqi Lin; Hongbing Song; Meng Xiao; Tingting Huang; Quanhong Zhu (Fuel, 2023)

Evaluation of imide substance from Streptomyces atratus PY-1 for the biocontrol of Phytophthora blight - Chaoqun Zang; Tingting Kong; Bingbing Liang; Xiaozhou Liu; Jinhui Xie; Ying Lin; Xue Pei; Shuyi Yu; Chunhao Liang (European Journal of Plant Pathology, 2023)

Muscle fiber plasticity, stress physiology, and muscle transcriptome determine the inter-individual difference of swimming performance in the large yellow croaker (Larimichthys crocea) - Siping Li; Xin Liu; Tingting Lin; Guangpeng Feng; Xiaoshan Wang; Dong Zhang (Aquaculture, 2023)

A contrast of Pb(II), Cd(II), and Cu(II) toxicities to Aspergillus niger through biochemical, morphological, and genetic investigations - Lin Zhang; Xin Yang; Sensen Li; Lingyi Tang; Tianyi Chen; Tingting Gu; Genqiang Chen; Geoffrey Michael Gadd; Zhen Li (Journal of Hazardous Materials, 2023)

Impact of biological activated carbon filtration and backwashing on the behaviour of PFASs in drinking water treatment plants - Tingting Zhong; Tao Lin; Xue Zhang; Fuchun Jiang; Han Chen (Journal of Hazardous Materials, 2023)

Linking pyrogenic carbon redox property to arsenite oxidation: Impact of N-doping and pyrolysis temperature - Dunfeng Si; Haotian Wu; Min Yang; Tingting Fan; Dengjun Wang; Lin Chen; Changyin Zhu; Guodong Fang; Song Wu; Dongmei Zhou (Journal of Hazardous Materials, 2023)

Polarity-extended composition profiling via LC-MS-based metabolomics approaches: A key to functional investigation of Citrus aurantium L - Wen Miao; Xiaojing Liu; Na Li; Xiqing Bian; Yiran Zhao; Jing He; Tingting Zhou; Jian-Lin Wu (Food Chemistry, 2023)

MiR-29a-3p inhibits high-grade transformation and epithelial–mesenchymal transition of lacrimal gland adenoid cystic carcinoma by targeting Quaking - Fei Xu; Meixia Jiang; Qin Tang; Jiaqi Lin; Xun Liu; Chuanli Zhang; Jinzhi Zhao; Yanjin He; Lijie Dong; Limin Zhu; Tingting Lin (Molecular Biology Reports, 2023)

Contaminant characterization at pesticide production sites in the Yangtze River Delta: Residue, distribution, and environmental risk - Mei Li; Qiang Chen; Lu Yang; Ya Zhang; Jinlin Jiang; Shaopo Deng; Jinzhong Wan; Tingting Fan; Tao Long; Shengtian Zhang; Yusuo Lin (Science of The Total Environment, 2023)

Histological types of lung cancer attributable to fine particulate, smoking, and genetic susceptibility - Xiaojie Wang; Tingting Wang; Junjie Hua; Miao Cai; Zhengmin Qian; Chongjian Wang; Haitao Li; Stephen Edward McMillin; Hannah E. Aaron; Chuanbo Xie; Hualiang Lin (Science of The Total Environment, 2023)

Raised potential earthquake and tsunami hazards at the North Sulawesi subduction zone after a flurry of major seismicity - Tingting Zheng; Qiang Qiu; Jian Lin; Xiaodong Yang (Marine and Petroleum Geology, 2023)

A new strategy: Inhibitory effect and mechanism of Cymbopogon martinii essential oil on Aspergillus flavus - Lizhen Lin; Shuaipeng Chen; Wenxin Xia; Tingting Li; Lin Dong; Yan Zhang; Yuanyuan Zhang; Hangying Li; Yunsheng Zhao; Xueyan Fu (Food Bioscience, 2023)

Enhanced catalytic CuCo2Se4/g-C3N4 nano-composites as counter electrodes for high-performance quantum dot sensitized solar cells - Tingting Zhang; Qiu Zhang; Quanhang Li; Fengyan Li; Lin Xu (Chemical Engineering Journal, 2023)

Transcriptome and methylome dynamics in the gills of large yellow croaker (Larimichthys crocea) during low-salinity adaption - Jian Yang; Minhai Liu; Tingting Zhou; Qi Li; Zhihua Lin (Frontiers in Marine Science, 2023)
DNA methylation is a critical epigenetic modification that dynamically regulates gene expression in organisms facing abiotic stress. However, few studies have comprehensively examined the role of DNA methylation in marine fish during environmental adaptation. Therefore, this study explored the methylome dynamics and DNA methylation regulation mechanisms in large yellow croaker ( Larimichthys crocea ) during low-salinity adaption. The methylation level in the gills was notably raised in the S-group (5‰ salinity) compared to C-group (25‰ salinity). A total of 109 differentially methylated promoter target genes and 581 differentially expressed genes were identified via whole-genome bisulfite sequencing (WGBS) and RNA-seq of gills in the two salinity groups, respectively. Moreover, 23 hypo-methylated/up-regulated differentially methylated genes (DMGs) and 28 hyper-methylated/down-regulated DMGs were identified through integrative analysis, which were mainly enriched in signal transduction, ion exchange, energy metabolism, and cytoskeleton system and other biological processes. Collectively, our findings suggested that low-salinity stress can induce adaptive genome-wide DNA methylation changes, which can in turn affect the transcription of genes in large yellow croaker during low-salinity adaptation. Therefore, our findings provide new insights into the regulatory mechanisms of marine fish in response to rapid environmental changes.

Microplastics are transferred by soil fauna and regulate soil function as material carriers - Yunchao Luo; Lin Wang; Tingting Cao; Junxiu Chen; Meiqi Lv; Sijie Wei; Shangxian Lu; Xingjun Tian (Science of The Total Environment, 2023)

Association of greenness exposure with coronary artery stenosis and biomarkers of myocardial injury in patients with myocardial infarction - Jieyu Wu; Manqing Luo; Na Lin; Zelin Huang; Tinggui Wang; Tingting Xu; Liwei Zhang; Zhebin You; Maoqing Lin; Kaiyang Lin; Xiaoxu Xie; Yansong Guo (Science of The Total Environment, 2023)

Polyethylene mulching film degrading bacteria within the plastisphere: Co-culture of plastic degrading strains screened by bacterial community succession - Peiyuan Wang; Jiaxi Liu; Siqi Han; Yufan Wang; Yifan Duan; Tingting Liu; Lijun Hou; Zengqiang Zhang; Li Li; Yanbing Lin (Journal of Hazardous Materials, 2023)

Sulfate-enhanced low-temperature activity of Pt/γ-Al2O3 for landfill gas deoxygen - Xinyu Yang; Zezhi Chen; Huijuan Gong; Feng Lin; Tingting Zhu; Ziyi Yang (Fuel, 2023)

Aberrant Topological Properties of Brain Functional Network in Children with Obstructive Sleep Apnea Derived from Resting-State fMRI - Tingting Ji; Xuemin Ren; Ting Long; Xiaodan Li; Lin Mei; Wentong Ge; Jie Zhang; Shengcai Wang; Yongli Guo; Zhifei Xu; Yun Peng; Jiangang Liu; et al. (Brain Topography, 2023)

Correction to: circ-CCND1 regulates the CCND1/P53/P21 pathway through sponging miR-138-5p in valve interstitial cells to aggravate aortic valve calcification - Fei Yan; Xiang Xie; Qiang Huo; Weimin Zhang; Tingting Wu; Daniyaer Dilimulati; Lin Shi (Journal of Physiology and Biochemistry, 2022)

circ-CCND1 regulates the CCND1/P53/P21 pathway through sponging miR-138-5p in valve interstitial cells to aggravate aortic valve calcification - Fei Yan; Xiang Xie; Qiang Huo; Weimin Zhang; Tingting Wu; Daniyaer·Dilimulati; Lin Shi (Journal of Physiology and Biochemistry, 2022)

Associations of exposure to lead and cadmium with risk of all-cause and cardiovascular disease mortality among patients with type 2 diabetes - Kai Zhu; Yuge Zhang; Qi Lu; Tingting Geng; Rui Li; Zhenzhen Wan; Xuena Zhang; Yujie Liu; Lin Li; Zixin Qiu; Meian He; Liegang Liu; et al. (Environmental Science and Pollution Research, 2022)

Application of iron oxyhydroxide to stabilize As(V) and phenylarsonic acid in contaminated soil: adsorption and the relevance to bioavailability - Zhenglai Huan; Jinlan Zhang; Pengfei Guo; Zuhong Lin; Jie Li; Zhifeng Li; Wenjing Zhao; Shengbin Cao; Yongbing Zhu; Tingting Zhang (Environmental Science and Pollution Research, 2022)

The consistent background color preference highlights the personality in the lined seahorse, Hippocampus erectus - Siping Li; Xin Liu; Tingting Lin; Dong Zhang; Xiong Zou (Frontiers in Marine Science, 2022)
Background color in aquaculture has been paid more attention due to the effect on fish growth, survival, health, and reproduction. In the present study, we evaluated the background color preference of the lined seahorse ( Hippocampus erectus ) and its relationship with personality. Preference was assessed over 10 consecutive days through allowing the lined seahorse to freely choose six different colored compartments, i.e., white, red, green, black, yellow, and blue backgrounds. To minimize the spurious preference response, the individual preference index (PI) was applied to calculate the preference intensity of the background colors. Preference reliability was further verified by a binary choice test through the choice for the most preferred or non-preferred color. Preference consistency under stress situation was assessed by a “knock-at-the-door” test as confining the seahorse in a transparent circle after a 30-s air exposure and measuring the proportion of knock toward different colored backgrounds. The personality was conjointly analyzed by new environment test and novel object test. Overall, the lined seahorse showed a general preference for white and blue while avoidance of black and red backgrounds at either unstressed or stressed situations. The shyer the seahorse was, the more preference for white background it displayed. Thus, white and blue background colors are recommended for culturing the lined seahorse. Furthermore, white color preference is a potential indicator in personality study of the lined seahorse.

Effects of different carbon sources and carbon–nitrogen ratios on the survival, growth, intestinal biochemical parameters, and water quality of seahorse juveniles cultured under zero-water exchange conditions - Tingting Lin; Yishan Cai; Xin Liu; Siping Li; Dong Zhang; Lianjun Xia (Aquaculture International, 2022)

H3K4me3 CUT&Tag and Transcriptome Analysis Reveal the Epigenetic Regulatory Landscape in Gill Tissue of Large Yellow Croaker (Larimichthys crocea) Under Low Salinity Stress - Jian Yang; Minhai Liu; Weiliang Shen; Tingting Zhou; Xiongfei Wu; Qi Li; Zhihua Lin (Frontiers in Marine Science, 2022)
H3K4me3 is an important histone modification that could influence DNA replication and RNA translation in response to abiotic stress. Here, RNA-seq analyses were conducted in gill tissues of large yellow croaker to identify the function of H3K4me3 under low salinity stress. Additionally, CUT&Tag analyses were performed to identify the genome-wide dynamic changes in H3K4me3 and explore the mechanisms by which H3K4me3 regulates gene expression. A total of 201 differentially expressed genes (DEGs) were identified between the 5‰ low salinity group (S-group) and 25‰ normal salinity group (C-group), among which 23 DEGs (11 up-regulated H3K4me3 targets and 12 down-regulated targets) were directly regulated by H3K4me3. Our findings thus describe the epigenetic regulatory landscape of H3K4me3 in gill of large yellow croaker during low salinity stress, and provide novel insights into the regulation mechanisms of H3K4me3 mediating the responses of aquatic animals to abiotic stress.

Probiotics Treatment of Leg Diseases in Broiler Chickens: a Review - Tingting Xu; Ke Yue; Chaodong Zhang; Xishuai Tong; Luxi Lin; Qinqin Cao; Shucheng Huang (Probiotics and Antimicrobial Proteins, 2022)

Spreading-rate dependence of hydroacoustic and teleseismic seismicity of ridge-transform systems: East Pacific Rise, Galapagos Ridge, and Mid-Atlantic Ridge - Tingting Zheng; Jian Lin; Qiu Zhong (Acta Oceanologica Sinica, 2022)

Differences of Macroalgal Consumption by Eight Herbivorous Coral Reef Fishes From the Xisha Islands, China - Peng Wu; Teng Wang; Yong Liu; Chunhou Li; Yayuan Xiao; Shannan Xu; Tingting Han; Lin Lin; Qiumei Quan (Frontiers in Marine Science, 2022)
Herbivorous fishes play an important role in preventing the overabundance of macroalgae on coral reefs. Understanding the feeding selectivity and consumption of macroalgae by herbivorous fishes can be challenging in studies of their ecological role in the preservation and recovery of coral reefs. Coral reef decline, macroalgal overgrowth and overfishing are clearly visible in the Xisha Islands, China. However, there are seldom studies on the feeding behaviors of herbivorous fishes in this area. We used microscopy, 18S rRNA high-throughput sequencing, and stable isotope analyses to comprehensively examine the diet of eight herbivorous reef fish species common in the Xisha Islands, including one parrotfish, two chub, two unicorn fish, and three rabbitfish. Based on microscopic examination, Siganus argenteus fed on the highest number of macroalgae species (five species), followed by Naso unicornis (four species). Kyphosus cinerascens , K. vaigiensis , N. unicornis and S. punctatissimus fed on the entire macroalgal thallus, indicating their greater ecological importance compared with species that only consume algal fronds. According to the 18S rRNA high-throughput sequencing of fish intestinal contents, cluster analysis revealed that consumed macroalgae composition from the eight fishes always grouped together based on the fish species, but with low similarity. K. vaigiensis removed the highest diversity of macroalgae species as well as the greatest quantity of macroalgae. Calotomus carolinus can consume the red alga Pneophyllum conicum , which is widely distributed on Indo-Pacific coral reefs and can overgrow and kill live corals. N. unicornis was found to occupy the lowest trophic position based on stable isotope analysis. Multi-technique analyses revealed that K. vaigiensis , N. unicornis and S. argenteus showed a high consumption potential of macroalgae, suggesting that they are the key browsers that should receive priority protection in the Xisha Islands. A diverse herbivorous fish fauna is also very important in the Xisha coral reefs. These results not only demonstrated the various functions of different herbivorous fish species in macroalgal removal, but also provided insights into the management of herbivorous fishes on the coral reefs of the South China Sea.

TRPV1 Suppressed NLRP3 Through Regulating Autophagy in Microglia After Ischemia-Reperfusion Injury - Yao Lin; Tingting Huang; Weimin Shen; Qiongyi Pang; Qingfeng Xie; Xiang Chen; Fengxia Tu (Journal of Molecular Neuroscience, 2022)

Zkscan3 affects erythroblast development by regulating the transcriptional activity of GATA1 and KLF1 in mice - Zixuan Li; Binjie Sheng; Tingting Zhang; Tian Wang; Dan Chen; Gangli An; Xingbing Wang; Huimin Meng; Lin Yang (Journal of Molecular Histology, 2022)
ZKSCAN3 encodes a zinc-finger transcription factor that regulates the expression of important genes and plays a significant role in tumor development, pathogenesis, and metastasis. However, its biological functions under normal physiological conditions remain largely unknown. In our previous studies, using flow cytometry, we found that the deletion of Zkscan3 may cause abnormal erythropoiesis. In this study, we found that, in a Zkscan3 knockout mice model, the number of splenic early-stage (basophilic-erythroblasts) and late-stage (chromatophilic-erythroblasts to polychromatophilic-erythroblasts through orthochromatophilic-erythroblasts) erythroblasts increased, whereas the number of late erythroblasts in the bone marrow decreased. Moreover, the phenotype was exacerbated after treating mice with phenylhydrazine (PHZ), which causes severe hemolytic anemia. In the knockout mice treated with PHZ, the percentage of reticulocyte in the peripheral blood conspicuously increased, whereas MCHC and red blood cells decreased. Then, we performed RNA-seq and quantitative-polymerase chain reaction assay and found that the expression of GATA1 and Tiam1 in erythroblasts were upregulated, whereas KLF1 was downregulated. Luciferase assays showed that Zkscan3 inhibited the transcription of GATA1 and Tiam1 and promoted the expression of KLF1 . Additionally, ChIP and CO-IP results confirmed that Zkscan3 directly interacts with GATA1 and inhibits its transcriptional activity in MEL cells. Our results demonstrate, for the first time, the significant role of Zkscan3 in physiological erythropoiesis through the interaction with GATA1, both at the DNA and protein level, and with Tiam1 and KLF1 at the DNA level.

Spatiotemporal variations of dissolved organic matter in a typical multi-source watershed in northern China: a fluorescent evidence - Baichuan Jin; Zuhong Lin; Weiyi Liu; Yong Xiao; Yuan Meng; Xiaolong Yao; Tingting Zhang (Environmental Science and Pollution Research, 2022)

Contribution of nitrogen sources to streams in mixed-use watershed varies seasonally in a temperate region - Zuhong Lin; Junchi Liu; Yong Xiao; Chaojie Yu; Jinlan Zhang; Tingting Zhang (Environmental Science and Pollution Research, 2022)

Algae, shrimp grazing, and fecal pellets synergistically increase microbial activity and enhance N immobilization during Typha angustifolia leaf litter decomposition - Xiangshi Kong; Can Wu; Bei Yao; Zaihua He; Hong Lin; Xingbing He; Yonghui Lin; Tingting Cao; Yanyan Jia; Yongfei Li; Kai Tian; Xingjun Tian (Environmental Science and Pollution Research, 2022)

Selenium Deficiency Leads to Changes in Renal Fibrosis Marker Proteins and Wnt/β-Catenin Signaling Pathway Components - Tingting Lin; Jiaqi Tao; Ying Chen; Yitong Zhang; Fenglan Li; Yutong Zhang; Xueqing Han; Zihui Zhao; Guiyan Liu; Hui Li (Biological Trace Element Research, 2022)

Rrn3 gene knockout affects ethanol-induced locomotion in adult heterozygous zebrafish - Fei Li; Jia Lin; Tingting Li; Jing Jian; Qi Zhang; Yinglan Zhang; Xiuyun Liu; Qiang Li (Psychopharmacology, 2022)

Simultaneous high-efficiency removal of sulfamethoxazole and zinc (II) from livestock and poultry breeding wastewater by a novel dual-functional bacterium, Bacillus sp. SDB4 - Xi Chen; Hai Lin; Yingbo Dong; Bing Li; Tingting Yin; Chenjing Liu (Environmental Science and Pollution Research, 2022)

Assessing relative density of carbonate granular soil via dynamic cone penetration field and model tests - Lan Lin; Sa Li; Liqiang Sun; Tingting Li; Jiangsong Yin (Marine Georesources & Geotechnology, 2021)

Does the female seahorse still prefer her mating partner after a period of separation? - Tingting Lin; Xin Liu; Dong Zhang (Journal of Fish Biology, 2021)
For species showing sexual monogamy, once one male and one female form a mating pair bond, they will be faithful to each other in subsequent breeding events. However, if their pair bond is broken for some reason, do they continue to prefer their partner when they come together again for mating? In other words, can the broken pair bond of sexually monogamous species be repaired? This is an interesting question but not yet well answered. To address this question, in the present study we used the lined seahorse ( Hippocampus erectus ), a typical sexually monogamous species, to study the partner preference of a female individual who experienced a complete separation followed by a reunion with her partner. Our main findings are as follows: (i) The female seahorse no longer prefers her partner after a separation, whether it is a former partner or a recent partner. No preference for partner‐males may indicate that the broken pair bond cannot be repaired. (ii) The female seahorse maintains sexual fidelity to her partner in the absence of separation. However, once the health of her partner decreases, the female will switch mate, and her courtship with the new partner can take place during the pregnancy of her original partner. The first finding may provide insight into whether monogamous species still have an opportunity to reselect a new partner in the future to correct their poor choice once they have mated with a low‐quality partner. The answer is that they can still gain an opportunity as long as the pair bonds with their current partners are broken. The second finding may reveal the conditions and timing at which a female seahorse switches her mate. These findings help us better understand the mating system of the seahorse H. erectus .

The Discovery of Circadian Rhythm of Feeding Time on Digestive Enzymes Activity and Their Gene Expression in Sinonovacula constricta Within a Light/Dark Cycle - Yanzi Liu; Hanhan Yao; Tingting Zhou; Zhihua Lin; Yinghui Dong (Frontiers in Marine Science, 2021)
The circadian rhythm has a great impact on the growth, metabolism and development of animals, but little is known about the circadian rhythm of marine bivalves. Understanding of the feeding rhythm is of great significance to increase the yield of razor clam Sinonovacula constricta , an economically important bivalve mollusk. The aim of this experiment was to study the effects of circadian rhythm of feeding time on digestive enzymes activities and their gene expression in S. constricta within a light (ZT8-ZT20)/dark (ZT20-ZT8) cycle. The present results showed that circadian rhythm of feeding rate (FR) was highly associated with digestive enzyme activities and relative expression of their genes. The highest values of FR were basically observed in the night from ZT0-ZT2 and ZT6-ZT8, which were significantly higher than those values in the daytime from ZT12-ZT14 and ZT18-ZT20 ( P < 0.05). The digestive enzymes activities displayed the highest values at ZT2 and ZT8, and the lowest at ZT14 and ZT20. Among them, cellulase and pepsin were found to have significantly different activities ( P < 0.05), rather than amylase and lipase. Notably, the relative expression of digestive enzyme genes shared the similar pattern with the activities of digestive enzymes. The highest values of relative gene expression of amylase ( AMY ), lipase ( LIP ), cellulase ( CEL ), and pepsin ( PEP ) were found at ZT2 and ZT8 in the night, while the lowest values were found at ZT14 during the day. It is therefore suggested that the biological clock may regulate the process from feeding to digestion. Furthermore, it might be better to feed at night to reduce cultivating cost and increase economic benefits in the farming industry of S. constricta .

Glucose-Responsive Polyelectrolyte Complexes Based on Dendritic Mesoporous Silica for Oral Insulin Delivery - Tingting Qin; Libiao Yan; Xin Wang; Siqi Lin; Qingbing Zeng (AAPS PharmSciTech, 2021)

RETRACTED ARTICLE: Antioxidative effects of polypyrimidine tract-binding protein-associated splicing factor against pathological retinal angiogenesis through promotion of mitochondrial function - Lijie Dong; Tingting Lin; Wenbo Li; Yaru Hong; Xinjun Ren; YiFeng Ke; Xiaomin Zhang; Xiaorong Li (Journal of Molecular Medicine, 2021)

Anti-Inflammatory Effects of an Extract from Pseudomonas aeruginosa and Its Purified Product 1-Hydroxyphenazine on RAW264.7 Cells - Jun Xiao; Aye Aye Thwe; Tingting Liu; Dafei Gong; Wanhua Lin; Changhua Shang; ZuJun Lu (Current Microbiology, 2021)

Air-pollutant mass concentration changes during COVID-19 pandemic in Shanghai, China - Zhi Niu; Tingting Hu; Lin Kong; Wenqi Zhang; Pinhua Rao; Dafeng Ge; Mengge Zhou; Yuseng Duan (Air Quality, Atmosphere & Health, 2021)

Not vegetation itself but mis-revegetation reduces water resources - Guoyi Zhou; Jun Xia; Ping Zhou; Tingting Shi; Lin Li (Science China Earth Sciences, 2021)

Prediction models of pulp components based on the quality indices in bleaching process - Zhichao Ma; Shaoxu Chen; Yongjun Yin; Xiaodan Lu; Yanying Zhou; Tingting Lin (Environment, Development and Sustainability, 2021)

A pentatricopeptide repeat protein DUA1 interacts with sigma factor 1 to regulate chloroplast gene expression in Rice - Yanxin Du; Weiping Mo; Tingting Ma; Weijiang Tang; Lijin Tian; Rongcheng Lin (Photosynthesis Research, 2021)

Association of Circulating and Aortic Zinc and Copper Levels with Clinical Abdominal Aortic Aneurysm: a Meta-analysis - Tingting Chen; Hongliang Zhang; Yang Zhang; Mengqi Yang; Juntao Wu; Minjun Yang; Jiangbo Lin; Weixu Gao; Lijiang Tang; Baohui Xu; Jianjun Jiang; Xiaofeng Chen (Biological Trace Element Research, 2021)

Selenium Deficiency-Induced Damage and Altered Expression of Mitochondrial Biogenesis Markers in the Kidneys of Mice - Hehuan Lai; Tingting Nie; Yitong Zhang; Ying Chen; Jiaqi Tao; Tingting Lin; Tangdong Ge; Fenglan Li; Hui Li (Biological Trace Element Research, 2021)

A novel streptonigrin type alkaloid from the Streptomyces flocculus CGMCC 4.1223 mutant Δ stnA/Q2 - Xiaozheng Wang; Fei Xu; Tingting Huang; Zixin Deng; Shuangjun Lin (Natural Product Research, 2020)

Production of gene-edited pigs harboring orthologous human mutations via double cutting by CRISPR/Cas9 with long single-stranded DNAs as homology-directed repair templates by zygote injection - Fei Xie; Xiaoyang Zhou; Tingting Lin; Lulu Wang; Chuanhong Liu; Xi Luo; Lihua Luo; Huayu Chen; Kenan Guo; Hong Wei; Yong Wang (Transgenic Research, 2020)

Activation of p62-Keap1-Nrf2 Pathway Protects 6-Hydroxydopamine-Induced Ferroptosis in Dopaminergic Cells - Yiran Sun; Libo He; Taoyu Wang; Wan Hua; Huan Qin; Jingjin Wang; Li Wang; Wanqin Gu; Tingting Li; Na Li; Xinanbei Liu; Fang Chen; et al. (Molecular Neurobiology, 2020)

Chemical composition, antioxidant, antimicrobial and anticancer activities of the essential oil from the rhizomes of Zingiber striolatum Diels - Minyi Tian; Tingting Liu; Xianghuan Wu; Yi Hong; Xiongli Liu; Bing Lin; Ying Zhou (Natural Product Research, 2020)

Gene UCHL1 expresses specifically in mouse uterine decidual cells in response to estrogen - Lishuang Hao; Di Song; Mengfei Zhuang; Yan Shi; Lin Yu; Yaping He; Jian Wang; Tingting Zhang; Zhaogui Sun (Histochemistry and Cell Biology, 2020)

Study on dynamic mechanical properties of phosphate rock through experimental tests and mesoscale simulation - Xiqi Liu; Gang Wang; Tingting Liu; Manqing Lin; Hongxia Lei; Abhay Kumar Mandal (Arabian Journal of Geosciences, 2020)

Pseudomonas syringae dual‐function protein Lon switches between virulence and metabolism by acting as both DNA ‐binding transcriptional regulator and protease in different environments - Canfeng Hua; Tingting Wang; Xiaolong Shao; Yingpeng Xie; Hao Huang; Jingui Liu; Weitong Zhang; Yingchao Zhang; Yiqing Ding; Lin Jiang; Xin Wang; Xin Deng (Environmental Microbiology, 2020)
Summary Lon, a member of the AAA+ protease family, plays vital roles in Type III secretion systems (T3SS), agglutination and colony shape in the model plant pathogen Pseudomonas syringae . Lon also functions as a transcriptional regulator in other bacterial species such as Escherichia coli and Brevibacillus thermoruber . To reveal the molecular mechanisms of Lon as a dual‐function protein in P . syringae , we studied Lon‐regulated genes by using RNA sequencing (RNA‐seq), chromatin immunoprecipitation sequencing (ChIP‐seq) and liquid chromatography–tandem mass spectrometry. As a transcriptional regulator, Lon directly regulated a group of genes (PSPPH_4788, gacA , fur , gntR , clpS , lon and glyA ) and consequently regulated their functions, such as 1‐dodecanol oxidation activity, motility, pyoverdine production, glucokinase activity, N‐end rule pathway, lon expression and serine hydroxymethyltransferase activity. Mass spectrometry results revealed that the expression levels of five T3SS proteins (such as HrcV, HrpW1) were higher in the ∆ lon strain than the wild‐type (WT) strain in KB. In MM, 12 metabolic proteins (such as AcdS and NuoI) showed lower levels in the ∆ lon strain than the WT strain. Taken together, these data demonstrate that the dual‐function protein Lon sophisticatedly regulates virulence and metabolism in P . syringa e.

Asymmetry in oceanic crustal structure of the South China Sea basin and its implications on mantle geodynamics - Fan Zhang; Jian Lin; Xubo Zhang; Weiwei Ding; Tingting Wang; Jian Zhu (International Geology Review, 2020)

Methamphetamine-Induced Cognitive Deficits and Psychiatric Symptoms Are Associated with Serum Markers of Liver Damage - Tingting Zhao; Changping Zhai; Hongmei Song; Yanhai Wu; Chuanhui Ge; Yonglin Zhang; Hongxia Xu; Zhengsuo Chi; Hui Chu; Wei Shi; Xiaodong Cheng; Xin Li; et al. (Neurotoxicity Research, 2020)

Chemical cues mediate social monogamy in a marine caridean shrimp, Lysmata debelius - Xin Liu; Dong Zhang; Tingting Lin; Zhenzhen Yan (Journal of Ethology, 2020)

Plants alter their vertical root distribution rather than biomass allocation in response to changing precipitation - Bingwei Zhang; Marc W. Cadotte; Shiping Chen; Xingru Tan; Cuihai You; Tingting Ren; Minling Chen; Shanshan Wang; Weijing Li; Chengjin Chu; Lin Jiang; Yongfei Bai; et al. (Ecology, 2019)
Elucidating the variation of allocation pattern of ecosystem net primary productivity ( NPP ) and its underlying mechanisms is critically important for understanding the changes of aboveground and belowground ecosystem functions. Under optimal partitioning theory, plants should allocate more NPP to the organ that acquires the most limiting resource, and this expectation has been widely used to explain and predict NPP allocation under changing precipitation. However, confirmatory evidence for this theory has mostly come from observed spatial variation in the relationship between precipitation and NPP allocation across ecosystems, rather than directly from the influences of changing precipitation on NPP allocation within systems. We performed a 6‐yr five‐level precipitation manipulation experiment in a semiarid steppe to test whether changes in NPP allocation can be explained by the optimal partitioning theory, and how water requirement of plant community is maintained if NPP allocation is unaltered. The 30 precipitation levels (5 levels × 6 yr) were divided into dry, nominal, and wet precipitation ranges, relative to historical precipitation variation over the past six decades. We found that NPP in both aboveground ( ANPP ) and belowground ( BNPP ) increased nonlinearly as precipitation increased, while the allocation of NPP to BNPP ( f BNPP ) showed a concave quadratic relationship with precipitation. The declined f BNPP as precipitation increased in the dry range supported the optimal partitioning theory. However, in the nominal range, NPP allocation was not influenced by the changed precipitation; instead, BNPP was distributed more in the surface soil horizon (0–10 cm) as precipitation increased, and conversely more in the deeper soil layers (10–30 cm) as precipitation decreased. This response in root foraging appears to be a strategy to satisfy plant water requirements and partially explains the stable NPP allocation patterns. Overall, our results suggest that plants can adjust their vertical BNPP distribution in response to drought stress, and that only under extreme drought does the optimal partitioning theory strictly apply, highlighting the context dependency of the adaption and growth of plants under changing precipitation.

Association analysis between feed efficiency and expression of key genes of the avTOR signaling pathway in meat-type ducks - Lei Yang; Tingting He; Yuan Xu; He Zang; Jiafa Wang; Zhiqiang Lin; Sihua Jin; Zhaoyu Geng (Molecular Biology Reports, 2019)

The effect of temperature on the developmental rates of seedling emergence and leaf-unfolding in two dwarf bamboo species - Shuyan Lin; Lijuan Shao; Cang Hui; Hardev S. Sandhu; Tingting Fan; Li Zhang; Fang Li; Yulong Ding; Peijian Shi (Trees, 2018)

Histological characterization of peppermint shrimp (Lysmata wurdemanni) androgenic gland - Xin Liu; Dong Zhang; Tingting Lin (Journal of Ocean University of China, 2017)

Identification of CHCHD10 Mutation in Chinese Patients with Alzheimer Disease - Tingting Xiao; Bin Jiao; Weiwei Zhang; Chuzheng Pan; Jingya Wei; Xiaoyan Liu; Yafang Zhou; Lin Zhou; Beisha Tang; Lu Shen (Molecular Neurobiology, 2017)

Effect of corticision on orthodontic tooth movement in a rat model as assessed by RNA sequencing - Qihui Gu; Shuyu Guo; Dongyue Wang; Tingting Zhou; Lin Wang; Zhendong Wang; Junqing Ma (Journal of Molecular Histology, 2017)

GATA4 regulates osteoblastic differentiation and bone remodeling via p38-mediated signaling - Tingting Zhou; Shuyu Guo; Yuxin Zhang; Yajuan Weng; Lin Wang; Junqing Ma (Journal of Molecular Histology, 2017)

Plasma levels of immune factors and sex steroids in the male seahorse Hippocampus erectus during a breeding cycle - Tingting Lin; Xin Liu; Dongxue Xiao; Dong Zhang (Fish Physiology and Biochemistry, 2017)

MicroRNA-150 targets ELK1 and modulates the apoptosis induced by ox-LDL in endothelial cells - Bing Qin; Yaqing Shu; Li Xiao; Tingting Lu; Yinyao Lin; Huan Yang; Zhengqi Lu (Molecular and Cellular Biochemistry, 2017)

Association of MMP-9 C-1562T polymorphism with risk of Henoch-Schönlein purpura nephritis in children of southeast China - Jinwen Xu; Liping Zhao; Hongxia Zhou; Tingting Ge; Lin Zhang (Genes & Genomics, 2017)

Characterization of BcMF23a and BcMF23b, two putative pectin methylesterase genes related to pollen development in Brassica campestris ssp. chinensis - Sue Lin; Li Huang; Xiaolin Yu; Xingpeng Xiong; Xiaoyan Yue; Tingting Liu; Ying Liang; Meiling Lv; Jiashu Cao (Molecular Biology Reports, 2017)

Serine 707 of APPL1 is Critical for the Synaptic NMDA Receptor-Mediated Akt Phosphorylation Signaling Pathway - Jiejie Wang; Wen Lu; Lin Chen; Ping Zhang; Tingting Qian; Wei Cao; Jianhong Luo (Neuroscience Bulletin, 2016)

Ordovician intrusive rocks from the eastern Central Asian Orogenic Belt in Northeast China: chronology and implications for bidirectional subduction of the early Palaeozoic Palaeo-Asian Ocean - Hongying Li; Zhiguang Zhou; Pengju Li; Da Zhang; Changfeng Liu; XiaoQi Zhao; Lizhen Chen; Congnan Gu; Tingting Lin; Mengmeng Hu (International Geology Review, 2016)

Gymnocypris przewalskii decreases cytosolic carbonic anhydrase expression to compensate for respiratory alkalosis and osmoregulation in the saline-alkaline lake Qinghai - Zongli Yao; Wenfei Guo; Qifang Lai; Jianquan Shi; Kai Zhou; Hongfang Qi; Tingting Lin; Ziniu Li; Hui Wang (Journal of Comparative Physiology B, 2016)

The RNA-binding protein Sam68 regulates tumor cell viability and hepatic carcinogenesis by inhibiting the transcriptional activity of FOXOs - Tingting Zhang; Chunhua Wan; Weidong Shi; Jian Xu; Hui Fan; Shusen Zhang; Zhipeng Lin; Runzhou Ni; Xiubing Zhang (Journal of Molecular Histology, 2015)

Carbonic anhydrase 2-like and Na+-K+-ATPase α gene expression in medaka (Oryzias latipes) under carbonate alkalinity stress - Zongli Yao; Qifang Lai; Zhuoran Hao; Ling Chen; Tingting Lin; Kai Zhou; Hui Wang (Fish Physiology and Biochemistry, 2015)

DNA Methylation Changes Induced in Rice by Exposure to High Concentrations of the Nitric Oxide Modulator, Sodium Nitroprusside - Xiufang Ou; Tingting Zhuang; Wenchao Yin; Yiling Miao; Bo Wang; Yunhong Zhang; Xiuyun Lin; Chunming Xu; Diter von Wettstein; Sachin Rustgi; Bao Liu (Plant Molecular Biology Reporter, 2015)

Mobilization of Diverse Transposable Elements in Rice Induced by Alien Pollination Without Entailing Genetic Introgression - Ying Wu; Tingting Jiang; Yue Sun; Zeyang Wang; Guizhen Guo; Shuai Sun; Jie Wang; Ning Li; Zhenhui Wang; Di Zhang; Yan Bai; Yang Gao; et al. (Plant Molecular Biology Reporter, 2015)

Metaproteomic analysis of bacterial communities in marine mudflat aquaculture sediment - Rui Lin; Xiangmin Lin; Tingting Guo; Linkun Wu; Wenjing Zhang; Wenxiong Lin (World Journal of Microbiology and Biotechnology, 2015)

Protective effects of hydroxysafflor yellow A (HSYA) on alcohol-induced liver injury in rats - Yanhao He; Qiang Liu; Yanxiang Li; Xiaofeng Yang; Weirong Wang; Tingting Li; Wei Zhang; Yuexin Cui; Chaoyun Wang; Rong Lin (Journal of Physiology and Biochemistry, 2015)

Effects of Traditional Chinese Medicine Fu Zheng Decoction on the Immunological Function and Clinical Prognosis of the Elderly Patients with Pneumonia - Hongqiang Li; Shumin Xu; Tingting Cheng; Lunxian Tang; Jianwen Bai; Minjia Lin (Cell Biochemistry and Biophysics, 2015)

A major QTL located on chromosome V associates with in vitro tuberization in a tetraploid potato population - Jun Zhou; Hui Fang; Jianwei Shan; Xiaoxi Gao; Lin Chen; Conghua Xie; Tingting Xie; Jun Liu (Molecular Genetics and Genomics, 2014)

Carbon and Nitrogen Metabolism in Leaves and Roots of Dwarf Bamboo (Fargesia denudata Yi) Subjected to Drought for Two Consecutive Years During Sprouting Period - Chenggang Liu; Yanjie Wang; Kaiwen Pan; Tingting Zhu; Wei Li; Lin Zhang (Journal of Plant Growth Regulation, 2014)

BODIPY Fluorescent Chemosensor for Cu2+ Detection and Its Applications in Living Cells: Fast Response and High Sensitivity - Li Quan; Tingting Sun; Wenhai Lin; Xingang Guan; Min Zheng; Zhigang Xie; Xiabin Jing (Journal of Fluorescence, 2014)

Halomonas zhaodongensis sp. nov., a slightly halophilic bacterium isolated from saline–alkaline soils in Zhaodong, China - Juquan Jiang; Yuanyuan Pan; Lin Meng; Shaoxin Hu; Xiaoxia Zhang; Baozhong Hu; Jing Meng; Cheng Li; Haipeng Huang; Kaibiao Wang; Tingting Su (Antonie van Leeuwenhoek, 2013)

Neuroprotective Effect of Resveratrol on Ischemia/Reperfusion Injury in Rats Through TRPC6/CREB Pathways - Yun Lin; Fang Chen; Jiancheng Zhang; Tingting Wang; Xin Wei; Jing Wu; Yinglu Feng; Zhongliang Dai; Qingping Wu (Journal of Molecular Neuroscience, 2013)

High-Level Expression of Sporamin in Transgenic Chinese Cabbage Enhances Resistance Against Diamondback Moth - Lin Qiu; Tingting Wu; Heng Dong; Linlin Wu; Jiashu Cao; Li Huang (Plant Molecular Biology Reporter, 2013)

Growth inhibition and apoptotic effect of alpha-eleostearic acid on human breast cancer cells - Tingting Zhang; Yanping Gao; Yu Mao; Quanbo Zhang; Caiyu Lin; Ping Lin; Jie Zhang; Xiujie Wang (Journal of Natural Medicines, 2012)

Regulation of GSK-3 beta in the proliferation and apoptosis of human thyrocytes investigated using a GSK-3 beta-targeting RNAi adenovirus expression vector: involvement the Wnt/beta-catenin pathway - Gang Chen; Qiqin Jiang; Zhenhui You; Jin Yao; Lunpan Mou; Xu Lin; Xiaoyan Shen; Tingting You; Qiang Lin; Junping Wen; Lixiang Lin (Molecular Biology Reports, 2010)

Preparation and physical properties of a novel biocompatible porcine corneal acellularized matrix - Yi Shao; Luowa Quyang; Yueping Zhou; Jing Tang; Yuehui Tan; Qiuping Liu; Zhirong Lin; Tingting Yin; Fangfang Qiu; Zuguo Liu (In Vitro Cellular & Developmental Biology - Animal, 2010)

High FFA-induced proliferation and apoptosis in human umbilical vein endothelial cell partly through Wnt/β-catenin signal pathway - Penli Zhu; Gang Chen; Tingting You; Jin Yao; Qiqin Jiang; Xu Lin; Xiaoyan Shen; Yufang Qiao; Lixiang Lin (Molecular and Cellular Biochemistry, 2010)

Free-air CO2 enrichment (FACE) enhances the biodiversity of purple phototrophic bacteria in flooded paddy soil - Youzhi Feng; Xiangui Lin; Yiming Wang; Jing Zhang; Tingting Mao; Rui Yin; Jianguo Zhu (Plant and Soil, 2009)

A collection of 10,096 indica rice full-length cDNAs reveals highly expressed sequence divergence between Oryza sativa indica and japonica subspecies - Xiaohui Liu; Tingting Lu; Shuliang Yu; Ying Li; Yuchen Huang; Tao Huang; Lei Zhang; Jingjie Zhu; Qiang Zhao; Danlin Fan; Jie Mu; Yingying Shangguan; et al. (Plant Molecular Biology, 2007)